Anode composition
By using high-purity microsilicon active material particles and anode composition of appropriate amounts of binder and conductive material in lithium-ion batteries, the mechanical degradation and interface instability of silicon anode due to volume changes are solved, and the stability of the anode is achieved and increase in cycle life.
Patent Information
- Application Number
- CN202380026048.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-07
- Filing Date
- 2023-03-07
- Publication Date
- 2024-12-20
AI Technical Summary
The silicon-based anode in lithium-ion batteries causes mechanical degradation and unstable interface of solid electrolytes due to significant volume changes, affecting cycle life.
Using an anode composition containing particles of high purity microsilicon active material, the BET surface area and particle size of the particles are within a specific range, combining adhesives and conductive materials to form a stable anode structure to control silicon expansion and degradation.
It significantly extends the stability and cycle life of the anode, and improves the long-term cycle stability and capacity retention of the battery.
Smart Images

Figure BDA0005031513460000281 
Figure BDA0005031513460000301 
Figure BDA0005031513460000311
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to anodes of lithium-ion batteries and anode compositions thereof. Specifically, the anodes of the present disclosure include an anode composition comprising micro-silicon active material particles, wherein the micro-silicon active material particles have low surface area and high purity. The present disclosure also relates to a method of incorporating the anode composition into an electrochemical cell. Background Art
[0002] Conventional lithium-ion (Li-ion) batteries typically use graphite-based anodes as the lithium intercalation material. However, silicon-based anodes offer improvements over graphite-based Li-ion batteries. 3.75 Si) exhibits higher gravimetric capacity (3579 mAh / g compared to 372 mAh / g for graphite) and volumetric capacity (about 2194 mAh / cm 3 Compared to about 750 mAh / cm in fully lithiated graphite 3 ). In addition, silicon-based anodes have a high + It has a low lithiation / delithiation voltage plateau of about 0.3-0.4 V, which allows it to maintain an open circuit potential that avoids undesirable Li plating and dendrite formation. Although silicon shows excellent electrochemical activity, it is challenging to achieve a stable cycle life for silicon-based anodes due to the significant volume change of silicon during lithiation and delithiation. Silicon active materials and regions may lose electrical contact with the anode because the significant volume change coupled with its low electrical conductivity separates silicon from the surrounding materials in the anode.
[0003] In addition, the significant volume change of silicon exacerbates the formation of a solid electrolyte interface (SEI), which may further lead to electrical isolation and, therefore, capacity loss. The expansion and contraction of silicon particles during charge-discharge cycles causes the silicon particles to pulverize, which increases the specific surface area of the silicon particles. As the silicon surface area changes and increases during cycling, the SEI repeatedly splits and reforms. Therefore, during cycling into a thick electronic and ionic insulating layer, the SEI continues to accumulate around the pulverized silicon area. This accumulated SEM increases the impedance of the electrode and reduces the electrochemical reactivity of the electrode, which is detrimental to the cycle life. Due to its high specific capacity, abundance, and low cost, silicon is a promising active material for Li-ion anodes. However, its significant volume change during lithiation and delithiation (Li 3.75 The volume change of Si1 phase (>280%) causes mechanical degradation of the electrode and unstable SEI, which leads to electrode swelling and poor battery cycle life.
[0004] Therefore, there is a need to provide new and alternative anode compositions for lithium-ion batteries, particularly lithium-ion batteries containing a majority of silicon active materials, which can control the expansion effects of silicon and significantly increase the stability and / or cycle life of the anode. Summary of the invention
[0005] The present disclosure provides an anode composition comprising micro-silicon active material particles, wherein the silicon content is at least 60 wt.% based on the total weight of the anode composition. The present disclosure also provides a method of incorporating an anode comprising the anode composition into an electrochemical cell and an electrochemical cell formed thereby, wherein the anode paired with the method of integration into the electrochemical cell can extend the stability and / or cycle life of the anode.
[0006] In one aspect, an anode composition is provided, comprising micro-silicon active material particles, wherein the micro-silicon active material particles have one or more of the following: (i) a BET surface area of about 0.1 m 2 / g and about 10m 2 / g, (ii)D 50 The particle size is between about 0.1 μm and about 10 μm, and (iii) D 50 The ratio of the BET surface area is between about 0.1 and about 10, and the amount of the micro-silicon active material particles present in the anode composition is between about 60 wt.% and about 95 wt.% based on the total weight % of the anode composition. In some embodiments, the amount of the micro-silicon active material particles present in the anode composition may be between about 70 wt.% and about 95 wt.% based on the total weight % of the anode composition. In some embodiments, the purity of the micro-silicon active material particles (excluding oxygen) may be at least 95 wt.%.
[0007] In some embodiments, the anode composition may further include one or more binders. The binder may be present in the anode composition in an amount of about 2.5 wt.% to about 15 wt.%, based on the total weight of the anode composition.
[0008] In some embodiments, the anode composition may further include one or more conductive materials. The conductive materials may be present in the anode composition in an amount of about 2.5 wt.% to about 40 wt.%, based on the total weight of the anode composition.
[0009] In some embodiments, the micro silicon active material particles and / or the anode composition may be pre-lithiated. The pre-lithiation level of the micro silicon active material particles and / or the anode composition may be from about 1% to about 30% silicon lithiated.
[0010] On the other hand, an electrochemical cell is provided, comprising: an anode; a cathode; an electrolyte; and a separator, wherein the anode comprises an anode composition defined in any one or more embodiments or examples described herein, wherein the lithium absorption capacity of the anode is greater than the lithium release capacity of the cathode. In some embodiments, during charging of a lithium-ion battery pack, the capacity of the lithium absorption capacity of the anode may not be fully utilized. In one example, the anode may be only partially lithiated in a fully charged state. In some embodiments, the degree of silicon lithiation may be limited to about 20% to about 80% of the theoretical maximum. In some embodiments, the capacity ratio of the anode to the cathode (N / P ratio) may be between about 1.05 and about 7. In other embodiments, the lower cutoff voltage may be between about 2.0V and 3.5V.
[0011] In some embodiments, the pre-lithiation level of the anode may be from about 1% to about 30% silicon lithiation. The cathode may be selected from the group consisting of lithium nickel cobalt manganese oxide (NCM), lithium iron phosphate (LFP), lithium nickel manganese spinel (LNMO), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium cobalt oxide (LCO) and sulfur composites. The electrolyte may be selected from a non-aqueous electrolyte solution comprising one or more lithium salts.
[0012] In some embodiments, the electrochemical cell may be an energy storage device. The energy storage device may be a battery, preferably a secondary battery. For example, the battery may be a lithium-ion battery.
[0013] In another aspect, a method for improving the cycling stability of a lithium ion battery is provided, the lithium ion battery having an anode and a cathode, at least one electrolyte and a separator, wherein the anode composition is defined by any one or more embodiments or examples described herein. In some embodiments, the anode in the battery delivers a specific capacity of at least about 450 mAh / g, 500 mAh / g, 600 mAh / g, 800 mAh / g, 1000 mAh / g, 1200 mAh / g or 1500 mAh / g, and retains at least about 80% of its initial capacity after 100, 200, 400, 600, 800, 1000 or 1500 cycles of the battery.
[0014] In another aspect, there is provided a use of an anode composition in an electrochemical cell, wherein the anode composition is at least partially applied to a current collector material, and wherein the anode composition is defined by any one or more embodiments or examples described herein.
[0015] In another aspect, a method for preparing an anode of an electrochemical cell is provided, the method comprising the steps of: (i) preparing an anode slurry comprising microsilicon active material particles, optionally one or more additional active materials, optionally one or more binders, optionally one or more conductive materials, optionally one or more additives and a solvent system; and (ii) casting a layer of the anode slurry onto a current collector material to provide a wet anode composition layer on the current collector material.
[0016] In another aspect, an anode prepared as defined in the method of any one or more embodiments or examples described herein is provided.
[0017] In another aspect, a method for assembling an electrochemical cell is provided, wherein the method comprises the following steps: preparing an anode defined by the method in any one or more embodiments or examples described herein, wherein the anode comprises an anode composition as defined in any one or more embodiments or examples described herein; and assembling the anode into an electrochemical cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Preferred embodiments of the present disclosure will be further described and illustrated, by way of example only, with reference to the accompanying drawings, in which:
[0019] Figure 1a is a series of graphs showing the specific coating capacity (anode) at C / 2 in a full cell (4 micro-Si anode samples).
[0020] Figure 1b is a graph showing the discharge capacity retention of a 30% capacity limited full cell at C / 2 rate (4 micro-Si anode samples).
[0021] Figure 2 It is a graph showing the half-cell capacity retention data of four micro-silicon anode samples.
[0022] Figure 3a is a graph showing the specific coating capacity at C / 2 for 70 wt% mSi (Elkem 2) limited capacity (at 35%, 51% and 99% Cap. Lim) full cells (anode).
[0023] Figure 3b is a graph showing the discharge capacity retention at C / 2 rate for 70 wt % mSi (Elkem 2) limited capacity (at 35%, 51% and 99% Cap. Lim) full cells.
[0024] Figure 4a is a graph showing the specific coating capacity of full cells of pre-lithiated 70 wt % mSi (Elkem 2) anodes (at 0, 10 and 20% pre-lithiation) at C / 2 rate.
[0025] Figure 4b is a graph showing the discharge capacity retention (Anode) at C / 2 for pre-lithiated 70 wt % mSi (Elkem 2) anodes (at 0, 10% and 20% pre-lithiation).
[0026] Figure 5a is a graph showing the specific coating capacity of 70 wt% mSi (Elkem 2) anodes with different binders (CMC / SBR vs. PAA) at C / 2 rate in 30% limited capacity full cells.
[0027] Figure 5b is a graph showing the discharge capacity retention at C / 2 rate for 70 wt % mSi (Elkem 2) anodes with different binders (CMC / SBR vs. PAA) in 30% limited capacity full cells.
[0028] Figure 6a is a graph showing the specific coating capacity at C / 2 for 70 wt % mSi (Elkem 2) anodes with Li0.25 PAA binder with and without CNTs (anode) versus Li0.95 PAA binder.
[0029] Figure 6b is a graph showing the discharge capacity retention at C / 2 for 70 wt % mSi (Elkem 2) anodes with Li0.25 PAA binder with and without CNTs (anode) versus Li0.95 PAA binder.
[0030] Figure 7a It is a graph showing the discharge capacity retention of a limited capacity full cell with micro-Si and PAA-copolymer at a C / 2 rate.
[0031] Figure 7b is a graph showing the specific coating capacity (anode) of Micro-Si and PAA-copolymer at C / 2 rate.
[0032] Figure 8a is a graph showing the specific coating capacity of 70 wt% vs. 90 wt% mSi (Elkem 2) anodes at C / 2.
[0033] Figure 8b is a graph showing the discharge capacity retention at C / 2 rate for 70 wt% vs. 90 wt% mSi (Elkem 2) anodes of limited capacity full cells.
[0034] Figure 9a is a graph showing the specific coating capacity of 70 wt % mSi (Elkem 2) anodes with and without CNTs at C / 2.
[0035] Figure 9b is a graph showing the discharge capacity retention at C / 2 for 70 wt % mSi (Elkem 2) anodes of limited capacity full cells with and without CNTs.
[0036] Fig.10a is a graph showing the specific coating capacity (anode) of a pre-lithiated (direct contact) 70 wt % mSi (Elkem 2) anode at C / 2 via a direct contact method.
[0037] Fig.10b is a graph showing the discharge capacity retention of a pre-lithiated (direct contact) 70 wt % mSi (Elkem 2) anode via a direct contact method full cell at C / 2 rate. DETAILED DESCRIPTION
[0038] The present disclosure describes the following various non-limiting examples relating to studies conducted to identify alternative and improved anodes comprising a predominantly micro-silicon anode composition for lithium-ion batteries, any methods of incorporating the anodes into electrochemical cells, the electrochemical cells so formed, and uses thereof.
[0039] General Definitions and Terminology
[0040] In the following description, reference is made to the accompanying drawings, which form a part of the present invention and show several embodiments by way of illustration. It is to be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure.
[0041] With respect to the definitions provided herein, unless otherwise stated or implied from the context, the defined terms and phrases include the meanings provided. In addition, unless otherwise expressly stated or apparent from the context, the following terms and phrases do not exclude that a person skilled in the relevant art has acquired the meaning of the term or phrase. These definitions are provided to help describe specific embodiments, and these definitions are not intended to limit the claimed invention, as the scope of the invention is limited only by the claims. In addition, unless the context otherwise requires, singular terms shall include the plural and plural terms shall include the singular.
[0042] All publications discussed and / or cited herein are incorporated in their entirety.
[0043] Throughout this disclosure, references to individual steps, compositions of matter, groups of steps, or groups of compositions of matter are to be considered to encompass both one and plural (i.e., one and more) of such steps, compositions of matter, groups of steps, or groups of compositions of matter, unless expressly stated otherwise or the context requires otherwise. Thus, as used herein, the singular forms "a," "an," and "the" include plural aspects unless the context expressly dictates otherwise. For example, reference to "a" includes a single as well as two or more; reference to "an" includes a single as well as two or more; reference to "the" includes a single as well as two or more, etc.
[0044] Those skilled in the art will appreciate that the present disclosure herein is susceptible to variations and modifications other than those specifically described. It should be understood that the present disclosure includes all such variations and modifications. The present disclosure also includes, individually or collectively, all examples, steps, features, methods, compositions and processes mentioned or indicated in this specification, as well as any and all combinations or any two or more of the steps or features.
[0045] The term "and / or", such as "X and / or Y", should be understood to mean "X and Y" or "X or Y", and should be considered to provide clear support for both meanings or either meaning.
[0046] Unless otherwise indicated, the terms "first," "second," etc. are used herein merely as labels and are not intended to impose order, position, or hierarchy requirements on the items to which these terms refer. Furthermore, reference to a "second" item does not require or preclude the existence of lower-numbered items (e.g., a "first" item) and / or higher-numbered items (e.g., a "third" item).
[0047] As used herein, when used with a list of items, the phrase "at least one of" means that different combinations of one or more of the listed items may be used, and only one of each item in the list may be needed. An item may be a specific object, thing, or category. In other words, "at least one of" means that any combination or any number of items in the list may be used, but not all items in the list will be needed. For example, "at least one of item A, item B, and item C" may mean item A; item A and item B; item B; item A, item B, and item C; or item B and item C. In some cases, "at least one of item A, item B, and item C" may mean, for example, but not limited to, two of item A, one of item B, and ten of item C; four of item B and seven of item C; or some other suitable combination.
[0048] It should be appreciated that certain features described herein in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features described in the context of a single embodiment for brevity may also be provided separately or in any sub-combination.
[0049] Throughout this specification, various aspects and components of the present invention can be presented in range format. The range format is included for convenience and should not be interpreted as a fixed limitation on the scope of the present invention. Therefore, unless otherwise specified, the description of the range should be considered to have clearly disclosed all possible sub-ranges and individual numerical values within the range. For example, the description of a range such as 1 to 5 should be considered to have specifically disclosed sub-ranges, such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 5, 3 to 5, etc., and individual numbers and partial numbers within the range, such as 1, 2, 3, 4, 5, 5.5 and 6, unless an integer is required or an integer is implied from the context. Regardless of the width of the disclosed range, this applies. Where specific values are required, these values will be indicated in the specification.
[0050] Throughout this specification, the word "comprise" or variations such as "comprises" or "comprising" should be understood to imply the inclusion of stated elements, integers or steps or groups of elements, integers or steps, but not the exclusion of any other elements, integers or steps or groups of elements, integers or steps.
[0051] Throughout the specification, the term "consisting essentially of is intended to exclude elements that would substantially affect the properties of the claimed composition.
[0052] In the present document, the terms "comprising", "comprise" and "comprises" are intended to be optionally replaced by the terms "consisting essentially of", "consist essentially of", "consists essentially of", "consisting of", "consist of" and "consists of", in each instance.
[0053] As used herein, the term "about" encompasses a tolerance of 10% of any value or values associated with the term.
[0054] Herein, the term "weight %" may be abbreviated as "wt. %".
[0055] Specific terms
[0056] As used herein, the term "lithiation" encompasses lithiation of either the anode or cathode and is intended to mean Li + Intercalated with or alloyed with active materials.
[0057] Herein, the term "delithiation" encompasses delithiation of the anode or cathode and is intended to mean Li + and extraction or dealloying of active materials.
[0058] The term "charge" can be used in the context of both full cells and half cells. In a full cell, the term "charge" covers the amount of charge that is forced to + A non-spontaneous process of migration from the cathode into the anode (initial pairing of the anode and cathode) and represents a rise in the cell voltage. In a half-cell, the term "charge" covers the extraction of Li from the working electrode. + The non-spontaneous process of deposition on the reference electrode (lithium metal foil) and indicating an increase in the cell voltage.
[0059] The term "discharge" can be used in the context of both full cells and half cells. In a full cell, the term "discharge" covers the extraction of Li from the anode. + The spontaneous process by which ions migrate from the anode to the cathode when assembled and represents a decrease in the cell voltage. In a half-cell, the term "discharge" covers the Li + Dissolution from the reference electrode (lithium metal foil) and Li + A spontaneous process that inserts into the working electrode and represents a decrease in the cell voltage.
[0060] As used herein, the term "half-cell" describes a reference test system consisting of a working electrode (electrode of interest) and a reference electrode (eg, lithium metal foil) used for research and development purposes.
[0061] As used herein, the term "full cell" describes a conventional electrochemical cell system that pairs a commercially relevant anode (graphite, silicon, LTO) with a commercially relevant cathode (LFP, LCO, NCM, NCA, LMO).
[0062] The term “prelithiation” describes the addition of Li to the cathode electrode prior to pairing with the cathode electrode in full cell format. + Inserted into the anode or anode active material.
[0063] The term "N / P ratio" or "negative-positive ratio" refers to the mass balance between the anode (negative electrode) and the cathode (positive electrode). The mass balance is calculated by the mass per cm of the respective electrodes. 2 Determined by the available area capacity.
[0064] The term "areal capacity" refers to the available capacity per unit area of the electrode (anode or cathode). This can be determined by the type and wt.% of active material in the coating and the amount of active material in mg / cm 2 (or g / m 2 The coating loading applied to the collector substrate is determined in mg / cm 2 The higher the load per cm 2 The higher the area capacity.
[0065] Anode composition
[0066] The present disclosure is directed to providing improvements in anodes for lithium-ion batteries. The present disclosure encompasses various studies and developments aimed at identifying and better understanding the failure mechanisms of anodes containing a majority of silicon anode compositions, and subsequently optimizing their formulations so that degradation (e.g., cracking and delamination) of the solid electrolyte interface, silicon particle fracture and instability can be controlled, reduced or in some way ameliorated to improve the stability and cyclability of lithium-ion batteries.
[0067] It has been unexpectedly discovered that, at least according to some examples as described herein, most silicon anode compositions can exhibit significant anode stability and / or cycle life. It has further been unexpectedly discovered that most silicon anode compositions paired with methods for integration into electrochemical cells can control SEI formation and silicon expansion and degradation, and thus significantly extend the stability and / or cycle life of the anode.
[0068] It has also been discovered that, at least according to some examples as described herein, a majority of silicon anode compositions for electrochemical cells (e.g., batteries) can provide one or more additional advantages, such as:
[0069] (a) Long-term cycling stability of lithium-ion (Li-ion) batteries;
[0070] (b) Controlled expansion and contraction of silicon during charge and discharge cycles of lithium-ion batteries, which minimizes silicon particle cracking, pulverization, and SEM growth;
[0071] (c) cell capacity fade during cycle life due to controlled silicon expansion / contraction and reduced silicon anode voltage window; and / or
[0072] (d) High rate capacity.
[0073] The anode composition described herein may include microsilicon active material particles, wherein the microsilicon active material particles have one or more of the following: (i) a BET surface area measured between about 0.1 m 2 / g and about 10m 2 / g; (ii) D 50The particle size is between about 0.1 μm and about 10 μm; and (iii) D 50 :BET surface area ratio is between about 0.1 and 10, and the amount of silicon present in the anode composition is between about 60 wt.% and about 95 wt.%, based on the total weight % of the anode composition.
[0074] The anode composition as described herein may include microsilicon active material particles, wherein the microsilicon active material particles have a BET surface area measured by (i) between about 0.1 m 2 / g and about 10m 2 / g; and (ii) D 50 The particle size is between about 0.1 μm and about 10 μm; or (iii) D 50 :BET surface area ratio is between about 0.1 and 10, and the amount of silicon present in the anode composition is between about 60 wt.% and about 95 wt.%, based on the total weight % of the anode composition.
[0075] The anode composition as described herein may comprise or consist of microsilicon active material particles as described herein, optionally one or more additional active materials, optionally one or more binders, optionally one or more conductive materials, and optionally one or more additives. In one example, the anode composition as described herein may comprise or consist of microsilicon active material particles, wherein the microsilicon active material particles have one or more of the following: (i) a BET surface area measured between about 0.1 m 2 / g and about 10m 2 / g; (ii) D 50 The particle size is between about 0.1 μm and about 10 μm; and (iii) D 50 : BET surface area ratio is between about 0.1 and about 10, and wherein the amount of microsilicon active material particles present in the anode composition is between about 60 wt.% and about 95 wt.% based on the total weight % of the anode composition; optionally one or more additional active materials; optionally one or more binders; optionally one or more conductive materials; and optionally one or more additives. In another example, the anode composition as described herein may include or consist of microsilicon active material particles, wherein the microsilicon active material particles have a BET surface area of (i) measured between about 0.1 m 2 / g and about 10m 2 / g; and (ii) D 50 The particle size is between about 0.1 μm and about 10 μm; or (iii) D 50:BET surface area ratio is between about 0.1 and about 10, and the amount of microsilicon active material particles present in the anode composition is between about 60wt.% and about 95wt.% based on the total weight % of the anode composition; optionally one or more additional active materials, optionally one or more binders; optionally one or more conductive materials; and optionally one or more additives.
[0076] In some embodiments or examples, the micro-silicon active material particle content of the anode composition may be about 60wt.% to about 95wt.%, based on the total weight of the anode composition. It should be understood that when the micro-silicon active material particle content of the anode composition is greater than 60wt.%, preferably greater than 70wt.%, additional advantages may be exhibited. The micro-silicon active material particle content may be less than about 95wt.%, 90wt.%, 85wt.%, 80wt.%, 75wt.%, 70wt.%, 65wt.% or 60wt.%. The micro-silicon active material particle content may be at least about 60wt.%, 65wt.%, 70wt.%, 75wt.%, 80wt.%, 85wt.%, 90wt.% or 95wt.%. The micro-silicon active material particle content of the anode composition may be within the range provided by any two of these upper and / or lower limits.
[0077] In some embodiments or examples, the thickness of the anode composition may be substantially uniform and in the range of about 5 μm to about 70 μm. The thickness (μm) of the anode composition may be less than about 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 or 5. The thickness (μm) of the anode composition may be at least about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70. The thickness of the anode composition may be within the range provided by any two of these upper and / or lower limits.
[0078] In some embodiments or examples, the anode composition may be loaded on the current collector material. In some embodiments or examples, the anode composition may be applied to the current collector material as a coating or film. It should be understood that the current collector may be at least partially coated with the anode composition. For example, the anode composition may be applied only to one side of the current collector material. The current collector material for the anode may be selected from the group comprising the following: copper, aluminum, stainless steel, titanium, carbon, perforated metal foil, metal foam, and porous and non-porous films based on metal-coated polymers. It should be understood that the current collector material will have appropriate size, porosity and pore size, covering the above materials and acting as a current collector. For example, the anode composition may be applied to a copper current collector material (such as copper foil). For example, a micro-silicon active material particle, one or more optional additional active materials, one or more optional adhesives, one or more optional conductive materials, and one or more optional additives or an anode composition consisting thereof may be loaded on a copper current collector material (such as copper foil). In some embodiments, the thickness of the current collector material for the anode may be between about 4 μm and about 25 μm. The thickness of the current collector (in μm) may be less than about 25, 20, 15, 10, 8, 6, or 4. The thickness of the current collector (in μm) may be at least about 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, or 25. The thickness of the current collector (in μm) may be within the range provided by any two of these upper and / or lower limits. In one example, the current collector material for the anode may be a copper foil having a thickness between about 6 μm and about 12 μm.
[0079] In some embodiments or examples, the anode composition can be an anode of a battery. For example, the anode composition can be an anode of a lithium-ion battery.
[0080] Silicon particles
[0081] The present invention relates to an anode composition comprising micro-silicon active material particles.
[0082] In some embodiments or examples, the micro silicon active material particles may be selected from the group consisting of: metallurgical silicon, polycrystalline silicon and single crystal silicon. In a preferred example, the micro silicon active material particles are metallurgical silicon.
[0083] It will be appreciated that the raw material for any type of elemental silicon is quartz sand (silicon dioxide (SiO2)). In conventional manufacturing processes, SiO2 is reacted with carbon in an electric arc furnace, where the carbon may be supplied to the process in the form of coke, and where high temperatures (about 1800°C) are applied to reduce SiO2 to Si and CO according to the following reaction:
[0084] SiO2+2C→Si+2CO…………………………………………(1)
[0085] This reaction produces metallurgical grade silicon, which may contain impurities such as Al, Ca, Fe, Ti, P, Cu, Cr, K, V, Ni, Na, etc. at levels ranging from hundreds to thousands of parts per million (ppm). Metallurgical silicon can be used in various industrial applications, including steel production. However, due to the impurities, it cannot be used in electronic applications. The crystal structure of metallurgical silicon is well defined, but it is neither as pure as single crystal silicon nor as efficient at conducting electricity as single crystal silicon. Metallurgical silicon has a metallic crystal structure, which is characterized by metallic bonding between its atoms. In a metallic crystal structure, the atoms are arranged in a repeating pattern, but lack order.
[0086] To reduce the impurities in metallurgical silicon to a few parts per billion (ppb), further refining is required. This process can produce semiconductor-grade or electronic-grade Si (also known as polysilicon). The reaction between metallurgical silicon and anhydrous HCl will form trichlorosilane (SiHCl3), which is a liquid with a boiling point of 32°C:
[0087] Si+3HCl→SiHCl3+H2…………………………………………(2)
[0088] It should be understood that some chloride impurities, such as FeCl3, may also be formed, but due to the difference between the boiling points of these impurities and SiHCl3, fractional distillation techniques can be used to separate the impurities. During this process, a mixture of SiHCl3 and chloride impurities is heated, with the vapors condensed in different distillation columns and maintained at appropriate temperatures. This will enable the separation of pure SiHCl3 from the impurities. The reaction between SiHCl3 and H2 will result in the formation of pure polysilicon.
[0089] 2SiHCl3+2H2→2Si+6HCl…………………………………………(3)
[0090] The crystal structure of polycrystalline silicon is ill-defined, and the small crystals (grains) that make up the material are randomly oriented and are typically less than 100 microns in size. The grains are separated by grain boundaries and typically have random crystal orientations. This produces a material that is weaker and less efficient at conducting electricity than single crystal silicon.
[0091] The Czochralski method is used to convert pure polysilicon into single crystals of single silicon. A seed crystal is required to grow the single crystal material, which will act as a template for growth. The Czochralski method involves heating the polysilicon in a quartz-lined graphite crucible by resistively heating it to the melting point of Si (1412°C). The seed crystal is then placed in the molten material and slowly raised, allowing the crystal to grow onto the seed crystal. During crystal growth, slow rotation is required to average out any temperature variations that may cause uneven solidification.
[0092] The resulting single crystal silicon is often referred to as single-crystalline silicon. It consists of silicon characterized by a regular and repeating arrangement of its atoms in a three-dimensional lattice and without grain confinement. Single crystal silicon can be considered an intrinsic semiconductor consisting only of superpure silicon. Silicon single crystals are well known for their high efficiency and high purity, making them ideal for electronic applications. By incorporating other elements, single crystal silicon can be p-type silicon and n-type silicon.
[0093] It is well known in the art that impurities may be present in any micro-silicon active material particles. It is also well known that impurities may be selectively added to any micro-silicon active material particles. In some embodiments, impurities selected from the group consisting of Al, Ca, Fe, Ti, P, Cu, Cr, K, V, Ni and Na may be present in the micro-silicon active material particles, for example, in a total amount or in an individual amount of less than about 5000 ppm, less than about 4500 ppm, less than about 4000 ppm, less than about 3500 ppm or less than about 3000 ppm. In one embodiment, the total impurities or individual impurities selected from the group consisting of Al, Ca, Fe, Ti, P, Cu, Cr, K, V, Ni and Na may be present in the micro-silicon active material particles in a range between about 0 ppm and about 5000 ppm, preferably between about 0 ppm and about 4000 ppm, and more preferably between about 0 ppm and about 3000 ppm.
[0094] In one embodiment, the microsilicon active material particles may be in any form, for example, the microsilicon active material particles may take the form of flakes, agglomerates, particles, powders, spheres, crushed materials, etc., and combinations thereof. The microsilicon active material particles may have any desired shape, including but not limited to cubes, rods, plates, polyhedrons, spheres or hemispheres, quasi-spheres, circles or semicircles, angles, irregular shapes, etc. In one embodiment, the aspect ratio (i.e., the ratio of length to width, where the length and width are measured perpendicular to each other and the length refers to the longest linear measurement dimension) of the microsilicon active material particles is 1.0 to 10.0, or 1.0 to 5.0, or 1.0 to 4.0, or 1.0 to 2.0. In one embodiment, the aspect ratio of the microsilica active material particles may be about 1.0 to 5.0, or about 1.0 to 4.0, or about 1.0 to about 3.0, or about 1.0 to about 2.0, such as about 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5.0.
[0095] In some embodiments, the particle size (in μm) of the microsilicon active material particles may be at least about 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, or 30. In some embodiments, the particle size (in μm) of the microsilicon active material particles may be less than about 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0.5. Combinations of any two or more of these upper and / or lower particle sizes are also possible, for example, the particle size (in μm) of the microsilicon active material particles may be between about 1 to about 10, about 2 to about 8, about 3 to about 6, or about 2 to about 5. The particle size is taken as the longest cross-sectional diameter across the microsilicon active material particles. For non-spherical microsilicon active material particles, the particle size is taken as the distance corresponding to the longest cross-sectional dimension across the particle.
[0096] The micro-silicon active material particles may have a certain particle size distribution, wherein 90% of the micro-silicon active material particles (D 90 ) has a particle size of less than about 34, 32, 30, 28, 24, 20, 18, 16, 14, 12, 10, 8, 6, 5 or 4 μm, wherein 50% of the microsilicon active material particles (D 50 ) has a particle size (in μm) of less than about 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.8, 0.6, 0.4, 0.2, 0.1, or 10% of the microsilicon active material particles (D 10 ) is less than about 4, 3, 2 or 1 μm. In some embodiments, the microsilicon active material particles have a particle size of (D 50 ) particle size (in μm) is at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. In some embodiments, the (D 50 ) particle size (in μm) is less than about 10, 9, 8, 7, 6, 5, 4, 3.5, 3, 2.5, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.5, 0.4, 0.3, 0.2 or 0.1. Combinations of any two or more of these upper and / or lower particle sizes are also possible, for example, the (D) of the microsilicon active material particles 50 ) particle size (in μm) is between about 0.1 to about 10, about 0.1 to about 9, about 0.1 to about 8, about 0.1 to about 7, about 0.1 to about 6, about 0.1 to about 5, about 0.5 to about 10, about 0.5 to about 9, about 0.5 to about 8, about 0.5 to about 7, about 0.5 to about 6, about 0.5 to about 5, about 1 to about 10, about 1 to about 9, about 1 to about 8, about 1 to about 7, about 1 to about 6, or about 1 to about 5 μm.
[0097] One or more advantages of the present disclosure are provided by microsilicon active material particles having a low surface area. It has been found that the more charge / discharge cycles the microsilicon is subjected to, the higher the surface roughness of the microsilicon particles, resulting in a higher surface area. The higher the surface area, the greater the loss of Li ions per cycle. This has a significant impact on the cycle life of the anode. It has been found that starting with a low surface area can mitigate this effect. In some embodiments or examples, the BET surface area of the microsilicon active material particles can be about 0.1 m 2 / g to about 10m 2 / g, for example about 1m 2 / g to about 5m 2 / g. The BET surface area of the micro-silicon active material particles (m 2 / g) can be at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 m / g. 2 In other embodiments or examples, the surface area (m 2 / g) may be less than about 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, or 0.1 m 2 / g. Combinations of these surface area values to form various ranges are also possible, for example, the surface area of micro-silicon active material particles (m 2 m / g) may be from about 0.1 to about 10, from about 0.1 to about 9, from about 0.1 to about 8, from about 0.1 to about 7, from about 0.1 to about 6, from about 0.1 to about 5, from about 0.5 to about 10, from about 0.5 to about 9, from about 0.5 to about 8, from about 0.5 to about 7, from about 0.5 to about 6, from about 0.5 to about 5, from about 1 to about 10, from about 1 to about 9, from about 1 to about 8, from about 1 to about 7, from about 1 to about 6, or from about 1 to about 5 m / g) may be from about 0.1 to about 10, from about 0.1 to about 9, from about 1 to about 8, from about 1 to about 7, from about 1 to about 6, or from about 2 / g.
[0098] The inventors unexpectedly found that the D 50 Particle size (in μm) and BET surface area (m 2 There is a relationship between the D / g of the micro-silicon active material particles and the ratio of these parameters to the electrochemical performance of the anode. 50 Particle size (in μm) and BET surface area (m 2 / g) may be in the range of about 0.1 to about 10. In some embodiments or examples, the D 50 Particle size (in μm) and BET surface area (m 2The ratio of D / g) may be at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. In some embodiments or examples, the D of the microsilicon active material particles is at least about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. 50 Particle size (in μm) and BET surface area (m 2 The ratio of D / g) can be less than about 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 or 0.1. Combinations of these ratios to form various ranges are also possible, for example, the D of the microsilicon active material particles is less than about 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2 or 0.1. 50 Particle size (in μm) and BET surface area (m 2 The ratio of D / g) may be in the range of about 0.1 to about 10, about 0.1 to about 9, about 0.1 to about 8, about 0.1 to about 7, about 0.1 to about 6, about 0.1 to about 5, about 0.5 to about 10, about 0.5 to about 9, about 0.5 to about 8, about 0.5 to about 7, about 0.5 to about 6, about 0.5 to about 5, about 1 to about 10, about 1 to about 9, about 1 to about 8, about 1 to about 7, about 1 to about 6, or about 1 to about 5. In a specific example, the D of the microsilicon active material particles is about 0.1 to about 10, about 0.1 to about 9, about 0.1 to about 8, about 1 to about 7, about 1 to about 6, or about 1 to about 5. 50 Particle size (in μm) and BET surface area (m 2 / g) is in the range of about 0.1 to about 6, and the ratio of the nanostructured carbon nanotubes to the nanostructured carbon nanotubes is about 2 μm to about 8 μm and about 1 μm, respectively. 2 / g to about 5m 2 / gD 50 The BET surface area range provides an improvement in the initial Coulombic efficiency and capacity retention of the anode. Specifically, the D 50 Particle size (in μm) and BET surface area (m 2 The ratio of the nanostructured carbon nanotubes to nanostructured carbon nanotubes is in the range of about 1.0 to about 3.5, and the nanostructured carbon nanotubes are in the range of about 3.0 μm to about 6.0 μm and about 1.0 μm, respectively. 2 / g to about 3.5m 2 / gD 50 The particle size and BET surface area ranges provide, advantageously, the maximum improved capacity retention in a full cell configuration of a micro-silicon anode design. It will be appreciated that when D 50 When the particle size / BET surface area ratio is higher than 3.5 and lower than 1.0, the electrochemical performance is found to decrease gradually. 50 Particle size ranges from 0.1 μm to 2.0 μm and BET surface area > 5 m 2 / g makes D 50When the particle size / BET surface area ratio is between 0.01 and 0.10, the ICE and capacity retention are found to drop sharply. Without wishing to be bound by theory, this phenomenon may be caused by the low surface reactivity of the micro-silicon active material particles with the electrolyte, thereby forming a thinner and less resistive SEI layer.
[0099] It is surprising to find that when various micro-Si anode grades are cycled in half-cell and full-cell designs, there is an inverse relationship in cycling stability, which is determined by their respective particle size, BET surface area, and d 50 The ratio between particle size and BET surface area is determined.
[0100] In the half-cell format tested under fully lithiated conditions, for d 50 >2.0μm, BET surface area <5m 2 / g and d 50 Rapid capacity degradation is evident for samples with particle size:BET surface area ratios above 0.01 to 0.1. The cycling stability observed from half-cell tests is reversed when the micro-Si materials are tested in a full-cell design with limited capacity. 50 Particle size (preferably 2.0-8.0 μm), low BET surface area (preferably 1.0-5.0 m 2 / g) and high d 50 Micro-silicon materials with a particle size:BET surface area ratio (preferably 0.1-6.0) produce stable cycling performance with higher ICE and capacity retention.
[0101] The expansion and contraction of silicon particles during charge-discharge cycles causes the silicon particles to pulverize, which increases the specific surface area of the silicon particles. In the half-cell, Li is supplied unlimitedly by the Li metal counter electrode. + In the case of a large Si surface area, a low average particle size and thus reduced stress on the particles make it possible to have a low d 50 , high BET surface area and d 50 Micro-Si particles with a particle size:BET surface area ratio < 0.1 will take longer to reach full depletion of the Si electrode, resulting in relatively stable cycling performance.
[0102] In the full cell design with limited Li reservoir, the 50 <2.0μm, BET surface area>5m 2 / g and d 50 The larger surface area of the micro-Si particles, which consist of a particle size:BET surface area ratio < 0.1, increases the reactivity during charge-discharge, resulting in Li +Consumption is accelerated, resulting in poor capacity retention and cycle life. 50 Particle size (preferably 2.0-8.0 μm), low BET surface area (preferably 1.0-5.0 m 2 / g) and high d 50 Li in micro-silicon materials with particle size: BET surface area ratio (preferably 0.1-6.0) + The low surface reactivity of ions and hence low irreversible consumption extend the capacity retention and cycle life. 50 The specific combination of MgO and BET surface area can lead to exceptionally good performance in full cells.
[0103] In an electrochemical full cell of limited capacity, the anode is designed so that its lithium uptake capacity is greater than the lithium release capacity of the cathode. This results in the lithium uptake capacity of the anode being not fully utilized, i.e., in a fully charged state, the silicon active material particles of the anode are only partially lithiated, and advantageously reduces or prevents the high volume changes typically found in silicon anodes during lithiation / delithiation cycles, which degrades its structure and shortens the life of the battery pack. In other words, a high N / P ratio may limit the degree of lithiation of the micro-silicon because the amount of Li ions is fixed by the cathode when the battery is assembled. For example, the anode may be significantly too large relative to the amount of lithium contained in the battery and provided by the cathode. Since the degree of lithiation is limited by an overly large anode, the level of expansion of the micro-silicon active material particles and their degradation are also limited.
[0104] In some embodiments or examples, the tap density of the micro-silicon active material particles may be about 0.5 g / cm 3 To about 1.5g / cm 3 The tap density of the microsilicon active material particles may be at least about 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.2, 1.3, or 1.5 g / cm 3 In other embodiments or examples, the tap density of the microsilicon active material particles may be less than about 1.5, 1.4, 1.3, 1.2, 1.0, 0.95, 0.9, 0.85, 0.8, 0.75, 0.7, 0.65, 0.6, 0.55, or 0.5 g / cm 3 Combinations of these density values to form various ranges are also possible. For example, the density of the micro-silicon active material particles can be between about 0.5 g / cm 3 To about 1.2g / cm 3 Density can be measured by any standard method, for example according to ASTM D7481-18.
[0105] Advantageously, the microsilicon active material particles of the present disclosure can be provided in high purity. In one embodiment or example, the purity of the microsilicon active material particles (excluding oxygen) may be in the range of about 95 to about 99.9 (by wt.%). The purity of the microsilicon active material particles (excluding oxygen) may be at least (by wt.%) about 95, 96, 97, 98, 99, 99.5 or 99.9. The purity of the microsilicon active material particles (excluding oxygen) may be less than (by wt.%) about 99.9, 99.5, 99, 98, 97, 96 or 95. The purity of the microsilicon active material particles (excluding oxygen) may be within the range provided by any lower limit and / or upper limit as previously described.
[0106] In one embodiment or example, the purity of the microsilicon active material particles (containing oxygen) may be in the range of about 79 to about 99.5 (by wt.%). The purity of the microsilicon active material particles (containing oxygen) may be at least (by wt.%) about 75, 80, 85, 90, 95, 96, 97, 98, 99 or 99.5. The purity of the microsilicon active material particles (containing oxygen) may be less than (by wt.%) about 99.5, 99, 98, 97, 96, 95, 90, 85, 80 or 75. The purity of the microsilicon active material particles (containing oxygen) may be within the range provided by any lower limit and / or upper limit as previously described.
[0107] The combination of novel and inventive features of the micro-silicon active material particles according to the present disclosure and their use in anode compositions for anodes in lithium-ion batteries unexpectedly leads to improvements in battery cycling behavior. It was unexpectedly shown that the lithium-ion battery as described herein has a small irreversible capacity loss in the first charging cycle and has stable electrochemical behavior and minimal decay in subsequent cycles. Therefore, by using micro-silicon active material particles as described herein, lower initial capacity loss and low continuous capacity loss of lithium-ion batteries can be achieved. Overall, the lithium-ion battery as described herein provides very good stability and cycle life. Therefore, a large number of cycles can be achieved with minimal fatigue, for example, fatigue caused by mechanical damage to the anode coating, anode material or SEI formation.
[0108] Pre-lithiation
[0109] The SEI layer is formed during lithium ion insertion, where the organic electrolyte is reduced on the surface of the anode when the anode potential is below about 1 V relative to Li+ / Li. The SEI layer is critical to preventing the electrolyte ions from being co-intercalated into the bulk electrode material by creating an electrically insulating but ionically conductive film. This prevents the electrolyte from continuing to decompose excessively. However, during the formation of the SEM layer film on the surface of the anode active material, some lithium ions may be irreversibly trapped in the electrode, resulting in lithium ion depletion.
[0110] The initial irreversible lithium loss of the anode can be compensated by adding lithium to the anode via pre-lithiation. Pre-lithiation methods can be roughly divided into electrochemical pre-lithiation and chemical pre-lithiation. Electrochemical pre-lithiation can be further divided into half-cell pre-lithiation or short-circuit pre-lithiation. Chemical pre-lithiation can be further divided into chemical synthesis, solution impregnation and mechanical processing. Additional pre-lithiation methods that can be used at the active material particles at the level of the anode coating are represented by chemical vapor deposition (CVD) type methods and physical vapor deposition methods (PVD). Preferred methods for pre-lithiating the anode composition include also pre-forming SEM layers and can be performed in a roll-to-roll process and are essentially cost-effective. It should be understood that the preferred pre-lithiation method for pre-lithiating the active material particles before incorporating the active material particles into the anode composition may be different from the method for pre-lithiating the anode composition. It should be noted that the present disclosure is not limited to a specific pre-lithiation method, and the most appropriate method will be selected to achieve the desired results.
[0111] Pre-lithiation can be applied to the anode electrode. For example, pre-lithiation can be applied to compensate for lithium lost in the first cycle, which constitutes one full charge and one full discharge of the electrochemical cell. If the amount of pre-lithiation is selected so that the SEI layer is formed before assembly into a full cell but no lithium is intercalated into the active material or alloyed with the active material, once incorporated into the full cell, the first cycle loss of the anode will be minimized, and any further loss of lithium is expected to be caused by other sources, such as the cathode electrode. As a result, the electrochemical cell now cycles at a higher cell capacity because more lithium is available in subsequent cycles to transfer back and forth between the anode and the cathode during repeated charge and discharge cycles.
[0112] In addition to compensating for any lithium loss that occurs during the first cycle and more generally the initial formation cycle, pre-lithiation can also provide a lithium reservoir in the anode before the anode is assembled into a battery assembly. The lithium reservoir can compensate for the lithium loss that continues over multiple cycles, thereby reducing capacity decay and extending the service life of the full battery. In other words, pre-lithiation can provide one or more advantages for silicon-containing anodes, especially anodes containing a high percentage of silicon. Providing a lithium reservoir to the anode using a method that also applies an SEI layer to the active material can also maximize the first cycle efficiency of the battery.
[0113] Optionally, the anode composition can provide a pre-lithiated anode composition. Pre-lithiation can occur at the anode active material level before incorporating the active material into the anode composition, or pre-lithiation can occur after preparing the anode composition. One or more advantages of the present disclosure are provided by a pre-lithiated anode composition that, once incorporated into a full cell arrangement, can provide a lithium reservoir in the anode, thereby compensating for the Li ions that persist during the charge / discharge cycle. + loss to extend its cycle life.
[0114] In some embodiments, the micro-silicon active material particles can be pre-lithiated micro-silicon active material particles, wherein the pre-lithiation occurs before the active material is incorporated into the anode composition. In other embodiments, the micro-silicon active material particles can be pre-lithiated micro-silicon active material particles, wherein the pre-lithiation occurs after the active material has been incorporated into the anode composition. The degree of pre-lithiation can be selected so that the phase produced is between Li0Si1 (0% pre-lithiation) and Li 3.75 Si1 or Li 4.40 Si1 (100% pre-lithiation). Any phase composition in between may be desirable, including Li1Si1, Li 1.71 Si2、Li2Si1、Li 3.5 Si1 and Li 3.75 Si1. In some embodiments or examples, the pre-lithiation amount of the micro-silicon active material particles and / or the anode composition may be between about 1% and about 30%. The pre-lithiation amount of the micro-silicon active material particles and / or the anode composition may be less than about 30%, 25%, 20%, 15%, 10%, 5%, or 1%. The pre-lithiation amount of the micro-silicon active material particles and / or the anode composition may be at least about 1%, 5%, 10%, 15%, 20%, 25%, or 30%. The pre-lithiation amount of the micro-silicon active material particles and / or the anode composition may be within the range provided by any two of these upper and / or lower limits.
[0115] The pre-lithiation of the micro-silicon active material particles can be carried out via physical vapor deposition (PVD) or chemical vapor deposition (CVD) or mechanical alloying process or chemical process or electrochemical process. It should be understood that before the pre-lithiated micro-silicon active material particles are incorporated into the anode composition, a series of suitable methods can be applied to produce a silicon-lithium alloy phase.
[0116] Additional active materials
[0117] The anode composition as described herein may further comprise one or more additional active materials. In some embodiments, the additional active material may be graphite or silicon. For example, flake graphite, natural graphite, artificial graphite, silicon oxide (SiOx) where x = 0.8 to 2, silicon-carbon composite materials, silicon alloys, or any combination thereof.
[0118] Adhesives
[0119] The anode composition as disclosed herein may further include one or more binders. The binder may be a polymer. In some embodiments, the polymer may be selected from the group consisting of: gum arabic; carboxymethyl cellulose (CMC) / citric acid; CMC / styrene-butadiene rubber (SBR); polytetrafluoroethylene (PTFE); polyvinylidene fluoride (PVDF); poly (1-trimethylsilyl-1-propyne) (PTMSP); gum binders such as gum arabic, xanthan gum and guar gum; natural cellulose-based binders; polysaccharides such as sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate; polyacrylates; aliphatic polymers such as polyvinyl butyral; aromatic polymers such as styrene-butadiene rubber. For example, the polymer can be selected from the group consisting of polyvinyl pyrrolidone, carboxymethyl cellulose, polyacrylic acid (PAA), poly(methacrylic acid), maleic anhydride copolymers including poly(ethylene and maleic anhydride) copolymers, polyvinyl alcohol, carboxymethyl chitosan, natural polysaccharides, xanthan gum, alginate, polyimide and PAA copolymers including one or more of the following: polyvinyl alcohol (PVA), polyurethane (PU), polyimide (PI) or polyacrylonitrile (PAN). In one example, the binder is PAA. The binder can be dissolved in H2O or ethanol or a mixture of H2O and ethanol or N,N' dimethylformamide or any other solvent suitable for the intended purpose. Some binders can exist in the form of water-based emulsions.
[0120] In some embodiments or examples, the ratio of the binder to the micro-silicon active material particles may be about 1:40, 1:35, 1:32, 1:30, 1:25, 1:23, 1:20, 1:15, 1:10, 1:9, 1:6 or 1:4. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:4 to about 1:32. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:8 to about 1:23. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:9 to about 1:15.
[0121] In some embodiments or examples, the binder (in wt.%) may be present in the anode composition in a range of about 2.5 to 15. The binder (in wt.%) may be present in the anode composition in an amount less than about 15, 12, 10, 8, 5, or 2.5. The binder (in wt.%) may be present in the anode composition in an amount of at least about 2.5%, 5%, 8%, 10%, 12%, or 15%. The amount of binder (in wt.%) present in the anode composition may be within the range provided by any two of these upper and / or lower limits. For example, the binder (in wt.%) may be present in the anode composition in a range of about 3 to about 8 or about 4 to about 8.
[0122] It has been found that the pH of the binder may affect the electrochemical performance of the anode composition. In some embodiments or examples, the pH of the binder may be less than 9, 8, 7, 6, 5, 4, 3 or 2. In some embodiments or examples, the pH of the binder may be at least 2, 3, 4, 5, 6, 7, 8 or 9. The pH of the binder may be within the range provided by any two of these upper and / or lower limits. For example, the pH of the binder may be in the range of 4 to 8. Preferably, a binder pH of less than 7 may be beneficial to the electrochemical performance of the micro-silicon anode, and may be due to (i) reduced corrosion of pure silicon in acidic regions and / or (ii) greater affinity of silicon to interact with the binder, such as PAA.
[0123] Conductive Materials
[0124] Anode compositions as described herein may further include one or more conductive materials. In some embodiments or examples, conductive materials may be carbon-based materials. In one embodiment or example, carbon-based materials may be nanoscale or micron-sized carbon particles or flakes, or a combination thereof. In one embodiment or example, carbon-based materials may be selected from the group consisting of activated carbon, carbon nanoparticles, graphite, single-walled (SWCNT) or multi-walled (MWCNT) carbon nanotubes, branched carbon nanotubes, carbon nanofibers, graphene, graphene oxide, MXene, nano- or micron-sized hard carbon, nano- or micron-sized porous carbon, and conductive polymers. Carbon-based materials may be selected from the group consisting of graphene, graphene oxide, graphite, single-walled (SWCNT) or multi-walled (MWCNT) carbon nanotubes, branched carbon nanotubes, carbon nanofibers, MXene, nano- or micron-sized hard carbon, nano- or micron-sized porous carbon, and conductive polymers. In an example, carbon-based materials may be carbon nanotubes.
[0125] In some embodiments or examples, the ratio of the conductive material to the micro silicon active material particles may be about 1:50, 1:48, 1:45, 1:40, 1:35, 1:30, 1:25, 1:20, 1:18, 1:15, 1:10, 1:8, 1:6, 1:4, 1:3, 1:2 or 1:1.3. The ratio of the conductive material to the micro silicon active material particles may be in the range of about 1:2 to about 1:30. The ratio of the conductive material to the micro silicon active material particles may be in the range of about 1:2 to about 1:18. The ratio of the conductive material to the micro silicon active material particles may be in the range of about 1:2 to about 1:15.
[0126] In some embodiments or examples, the conductive material may be present in the anode composition in the range of about 2.5 to 40 wt.% (based on the total weight of the anode composition). The conductive material may be present in the anode composition in an amount of less than about 40 wt.%, 30 wt.%, 20 wt.%, 15 wt.%, 10 wt.%, 7 wt.%, 5 wt.% or 2.5 wt.% (based on the total weight of the anode composition). The conductive material may be present in the anode composition in an amount of at least about 2.5 wt.%, 5 wt.%, 7 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 30 wt.% or 40 wt.% (based on the total weight of the anode composition). The conductive material may be present in the anode composition in an amount provided by any two of these upper and / or lower limits. For example, the conductive material may be present in the anode composition in an amount of about 7 wt.% to about 25 wt.%.
[0127] Electrochemical Cells
[0128] The present disclosure is directed to providing improvements in anodes for electrochemical cells. In some embodiments or examples, the present disclosure is directed to an anode for an electrochemical cell, the anode comprising an anode composition according to at least some embodiments or examples as described herein.
[0129] In some embodiments or examples, the electrochemical cell may comprise: a negative electrode, a positive electrode, at least one electrolyte, and a separator, wherein the anode comprises an anode composition as defined herein. For example, the electrochemical cell may comprise or consist of: an anode; a cathode; at least one electrolyte, the at least one electrolyte comprising one or more electrolyte solvents; and a separator, wherein the anode comprises an anode composition as defined herein, and wherein the lithium uptake capacity of the anode is greater than the lithium release capacity of the anode.
[0130] One or more advantages of the present disclosure are provided by the arrangement of the anode and cathode in an electrochemical cell, which has been found to be very important in increasing the stability and cycle life of the anode compositions described herein.
[0131] In some embodiments, capacity limitation can be considered based on mass loading or area capacity. Mass loading or area capacity refers to an electrochemical cell assembly in which the capacity of the anode may be significantly too large relative to the cathode. Capacity limitation may limit the capacity of an overly large electrode (anode) by allowing only partial lithiation to occur, because the amount of lithium contained in the electrochemical cell is limited by the lithium contained in the cathode when the cell is assembled. For example, in an electrochemical cell assembly in which the anode has an area capacity of x and the cathode has an area capacity of y, the estimated capacity limitation percentage generated is calculated by y / x*100. It should be understood that this capacity limitation method may be particularly useful in the case where the anode contains a high percentage of elemental silicon as an active material, which provides a specific capacity of more than 3500mAh / g.
[0132] It should be understood that the specific area capacity (in mAh / cm 2 The specific loading weight (in mg / cm2) provided by the amount of anode composition applied to the current collector corresponds to 2 Specific load weight (in mg / cm 2 The specific area capacity (in mAh / cm2) is based on the total weight of the anode composition, which includes micro-silicon active material particles, one or more optional additional active materials, one or more optional binders, and one or more optional conductive materials. 2 The silicon content in the anode composition is in units of silicon (in units) depending on the thickness of the anode composition coating on the current collector, the silicon content in the anode composition and the utilization of silicon.
[0133] In some embodiments, the specific areal capacity (in mAh / cm2) corresponding to complete utilization of the active material contained in the anode composition of the anode is 2 The unit is between 2.5 mAh / cm 2 Up to 20mAh / cm 2 between.
[0134] In some embodiments, the specific loading weight (in mg / cm 2 Units) can be between 0.95mg / cm 2 Up to 7.5 mg / cm 2 between.
[0135] In some embodiments, the anode and cathode are arranged in such a manner that the anode can deliver about 0.5 mAh / cm 2 to about 6 mAh / cm 2, and the anode can deliver about 1500mAh / g, 1200mAh / g, 1000mAh / g, 800mAh / g, 600mAh / g, 500mAh / g or 400mAh / g. In another embodiment, the anode and the cathode are arranged in such a way that the anode can deliver about 0.5mAh / cm 2 to about 6 mAh / cm 2 , and the anode may be used for about 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25% or 20%.
[0136] In other embodiments, the capacity limitation can be considered based on the phase composition of the LiSi alloy. 3.75 Si1 or Li 4.4 Si1 corresponds to a maximum achievable capacity of 3590 mAh / g or a maximum theoretical lithiation state of 4200 mAh / g. It should be understood that if the utilization of the anode is limited, this can be translated into a specific phase composition of the LiSi alloy. The specific phase composition can also be translated into specific capacity (mAh / g). For example, Li 1.71 Si1 can correspond to a specific capacity of up to 1636 mAh / g, Li 2.33 Si1 can correspond to a specific capacity of up to 2227 mAh / g, Li 3.25 Si1 can correspond to a specific capacity of up to 3101 mAh / g, Li 3.75 Si1 can correspond to a specific capacity of up to 3579 mAh / g, and Li 4.4 Si1 can correspond to a specific capacity of up to 4199 mAh / g.
[0137] In another embodiment, the capacity limitation may be considered based on the voltage of the anode during charge and / or discharge. It should be understood that the amount of silicon lithiation after discharge may be configured by the discharge voltage of the anode.
[0138] For example, it will be appreciated that the N / P ratio balance between the anode and cathode may be between about 1.05 and about 7, and / or that the voltage range may be controlled relative to the discharge level of the electrochemical cell. In some embodiments or examples, the capacity of the lithium uptake capacity of the anode may not be fully utilized during charging of a lithium-ion battery. In some embodiments or examples, the specific area capacity of the anode may be greater than the specific area capacity of the cathode. In other words, the anode is only partially lithiated in a fully charged state. Fully charged refers to the state of an electrochemical cell (e.g., a Li-ion battery) in which the anode, specifically the micro-silicon active material, has its highest degree of lithiation according to the present disclosure described herein. Partial lithiation of the anode means that the maximum lithium uptake capacity of the anode active material in the anode is not fully utilized. In some embodiments, the amount of lithium stored in the cathode (mAh / cm 2) can be compared to the lithium storage capacity of the anode (mAh / cm 2 ) is at least 2 times smaller. For example, the amount of lithium stored in the cathode (mAh / cm 2 ) can be the lithium storage capacity of the anode (mAh / cm 2 ) is 0.05 to 7 times.
[0139] In some embodiments, the Li / Si ratio of an electrochemical cell (e.g., a Li-ion battery) may be set by an anode to cathode ratio (N / P). In some embodiments, the N / P ratio between the anode and cathode may be between about 1.05 and about 7, about 2 and about 5, or about 3 and about 4. The N / P ratio may be greater than about 7, 6, 5, 4, 3, 2, or 1.05. The N / P ratio may be at least about 1.05, 2, 3, 4, 5, 6, or 7. The N / P ratio may be within a range provided by any two of these upper and / or lower limits. For example, the N / P ratio between the anode and cathode may be between about 1.5 and about 4 or between about 1.8 and about 3.5.
[0140] In some embodiments, the capacity limit (in %) may be at least about 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, or 99. In some embodiments, the capacity limit (in %) may be less than about 99, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20. The capacity limit (in %) may be within the range provided by any two of these upper and / or lower values. For example, the capacity limit (in %) may be between about 25 and about 90, or between about 30 and about 80.
[0141] The present disclosure advantageously provides an electrochemical cell designed so that the lithium uptake capacity of the anode is greater than the lithium release capacity of the cathode. This results in the lithium uptake capacity of the anode being not fully utilized, that is, in a fully charged state, the silicon active material particles of the anode are only partially lithiated, and advantageously reduces or prevents the high volume changes commonly found in silicon anodes during lithiation / delithiation cycles, which degrades its structure and shortens the life of the battery pack. In other words, a high N / P ratio may limit the degree of lithiation of micro-silicon because the amount of Li ions is fixed by the cathode when the battery is assembled. For example, the anode may be significantly too large relative to the amount of lithium contained in the battery and provided by the cathode. Since the degree of lithiation is limited by an overly large anode, the expansion level of the micro-silicon active material particles and their degradation are also limited. In some embodiments or examples, the degree of silicon lithiation may be in the range of about 20% to about 80%. Unexpectedly, the degree of silicon lithium within this range may have a stabilizing effect on the performance of the electrochemical cell.
[0142] In another embodiment, the capacity of the electrochemical cell can be limited by limiting the lower cutoff voltage. In some embodiments or examples, the lower cutoff voltage can be between about 2.5V and about 3.0V. For example, the lower cutoff voltage can be between 2.8V and about 3.0V. It should be understood that the voltage limit can be imposed by limiting the lower cutoff voltage. This can prevent the micro-silicon active material particles from completely de-lithiating at each cycle and reduce their expansion, thereby reducing degradation and thus extending the cycle life.
[0143] In another embodiment, the capacity of the electrochemical cell can be limited by limiting the upper cutoff voltage. In some embodiments or examples, the upper cutoff voltage can be between about 3.6V and about 4.25V.
[0144] It will be appreciated that both capacity and voltage limitations may be used simultaneously.
[0145] It should be understood that the anode composition may be pre-lithiated as described in any one or more of the embodiments or examples described herein. In some embodiments, pre-lithiation may occur before the active material is incorporated into the anode composition. In other embodiments, pre-lithiation may occur after the active material has been incorporated into the anode composition. Pre-lithiation may be performed by direct contact between lithium metal and the active anode material in the electrolyte. Due to the potential difference between the lithium metal and the anode material, an electric field is formed, which will enable electrons to transfer from a low potential area to a high potential area at the contact point under the action of the electric field. In an electrically neutral environment, the Li metal will release lithium ions, which pass through the electrolyte and are embedded in the anode material. For direct contact pre-lithiation methods, lithium metal powder or lithium metal foil can be used. During pre-lithiation, the lithium metal foil or powder will self-discharge upon contact, which is a relatively simple and effective process. In some embodiments or examples, the pre-lithiation amount of the anode composition may be between about 1% and about 30%. The pre-lithiation amount of the anode composition may be less than about 30%, 25%, 20%, 15%, 10%, 5%, or 1%. The pre-lithiation amount of the anode composition may be at least about 1%, 5%, 10%, 15%, 20%, 25%, or 30%. The pre-lithiation amount of the anode composition may be within a range provided by any two of these upper and / or lower limits.
[0146] In some embodiments, the amount of lithium contained in the anode may be about 30% of its maximum storage capacity, while the amount of lithium contained in the cathode may be 100% of its maximum storage capacity. In some embodiments, the amount of lithium contained in the anode may be about 20% of its maximum storage capacity, while the amount of lithium contained in the cathode may be 100% of its maximum storage capacity. In some embodiments, the amount of lithium contained in the anode may be about 10% of its maximum storage capacity, while the amount of lithium contained in the cathode may be 100% of its maximum storage capacity.
[0147] In one embodiment, for electrochemical pre-lithiation, a half-cell approach may be used. The silicon-containing electrode is assembled in a half-cell setup using a lithium foil reference electrode, and the degree of pre-lithiation is controlled by setting appropriate parameters in a constant current charge / discharge cycle program. In order to produce an SEI layer and a lithium reservoir of up to 30% lithium in the anode, the half-cell will undergo a first cycle by partially or fully lithiating the silicon-containing electrode followed by complete delithiation.
[0148] When a lithium reservoir is produced in the anode, a lithium reservoir that is partially lithiated to the desired degree is required. According to the composition of the silicon-containing anode and the relevant material properties, the first cycle loss can be estimated when the corresponding composition is tested for the lithium metal foil reference electrode in the half-cell and the anode composition first cycle loss is determined in this way. If the first cycle loss is estimated to be x%, then in order to produce a y% lithium reservoir, the initial lithiation step during the pre-lithiation process required to achieve the lithiation level of the z% silicon anode composition needs to consider x% + y%. If in a specific embodiment, the anode composition shows a 10% first cycle loss, this loss needs to be considered when calculating the desired pre-lithiation degree to obtain the resulting lithium reservoir. For example, in order to achieve a 10% lithium reservoir, the anode can be lithiated up to 20% of its expected design capacity (mAh / g), of which the initial approximately 10% is intended to compensate for the irreversible lithium loss during the first cycle, and the additional lithium reservoir is stored in the anode or silicon material to form the desired lithium reservoir. It should be understood that higher levels of pre-lithiation can be applied to achieve other desired levels of lithium reservoirs. The maximum desired level of lithium storage may be 30%.
[0149] It has been found that pairing pre-lithiation and capacity limitation can provide one or more additional advantages to the electrochemical cells of the present disclosure. For example, despite any lithium loss during the first cycle, the anode capacity occupied by lithium supplied by the cathode and stored in the anode will be the same with and without pre-lithiation, but the lithium reservoir in the anode can compensate for the gradual loss of lithium during repeated charge and discharge cycles over multiple cycles.
[0150] In some embodiments, the anode composition can be applied to a current collector material as a coating or film. The current collector material for the anode can be selected from the group comprising: copper, aluminum, stainless steel, titanium, carbon, perforated metal foil, metal foam, and porous and non-porous films based on metal-coated polymers. For example, the anode composition can be applied to a copper current collector material (e.g., copper foil). It should be understood that the current collector material will have an appropriate size, porosity, and pore size, covering the above materials and acting as a current collector.
[0151] In some embodiments, the thickness of the current collector material for the anode may be between about 4 μm and about 25 μm. The thickness of the current collector (in μm) may be less than about 25, 20, 15, 10, 8, 6 or 4. The thickness of the current collector (in μm) may be at least about 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20 or 25. The thickness of the current collector (in μm) may be within the range provided by any two of these upper and / or lower limits. In one example, the current collector material for the anode may be a copper foil having a thickness between about 6 μm and about 12 μm.
[0152] In some embodiments, the thickness of the anode composition may be substantially uniform and in the range of about 5 μm to about 45 μm. The thickness (μm) of the anode composition may be less than about 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 or 5. The thickness (μm) of the anode composition may be at least about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70. The thickness of the anode composition may be within the range provided by any two of these upper and / or lower limits.
[0153] It should be understood that the cathode active material is also applied to the current collector material. The current collector material for the cathode can be selected from the group comprising: aluminum, stainless steel carbon, perforated metal foil, metal foam, and porous and non-porous films based on metal-coated polymers. It should be understood that the current collector material will have an appropriate size, porosity, and pore size, covering the above materials and acting as a current collector. For example, the cathode composition can be applied to an aluminum current collector material (e.g., aluminum foil).
[0154] In some embodiments, the thickness of the current collector material for the cathode may be between about 10 μm and about 30 μm. The thickness of the current collector (in μm) may be less than about 30, 25, 20, 15 or 10. The thickness of the current collector (in μm) may be at least about 10, 12, 14, 16, 18, 20, 25 or 30. The thickness of the current collector (in μm) may be within the range provided by any two of these upper and / or lower limits. In one example, the current collector material for the cathode may be an aluminum foil with a thickness between about 10 μm and about 30 μm.
[0155] In some embodiments, the cathode may be selected from the group consisting of lithium nickel cobalt manganese oxide (NCM), lithium iron phosphate (LFP), lithium nickel manganese spinel (LNMO), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium cobalt oxide (LCO), and sulfur or a sulfur composite material including a mixture of sulfur and carbon.
[0156] In some embodiments or examples, the electrolyte may be selected from a non-aqueous solution of one or more lithium salts (e.g., in a Li-ion battery). One or more lithium salts may be selected from the group consisting of: lithium bis(trifluoromethanesulfone)imide, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium bis(trifluorosulfonylimide), lithium trifluoromethanesulfonate, lithium fluoroalkylsulfonylimide, lithium fluoroarylsulfonylimide, lithium bis(oxalatoborate), tris(trifluoromethylsulfonylimide)methyl lithium, lithium difluoromethanesulfonate, lithium trifluoromethanesulfonate salt (lithium trifluoromethanesulfonate), lithium bis(oxalate)borate, lithium tetrafluoroborate, lithium perchlorate, lithium tetrachloroaluminate, lithium hexafluoroarsenate, lithium hexafluoroantimonate, 4,5-dicyano-2-(trifluoromethyl)imidazolidine (LiTDI), LiPF3(C2F5)3(LiFAP), LiBF3(C2F5), lithium chloride, and combinations thereof. For example, the electrolyte may include lithium hexafluorophosphate.
[0157] In some embodiments or examples, the lithium salt is soluble in an organic solvent. The lithium salt is soluble in an organic solvent selected from ethers, esters, carbonates and acetals. In one example, the solvent can be selected from dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, dimethyl carbonate, tetrahydrofuran and dioxolane. In some embodiments or examples, the lithium salt can be dissolved in an organic solvent selected from the group consisting of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, dipropyl carbonate, cyclopentanone, sulfolane, dimethyl sulfoxide, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, 1,2-diethoxymethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 1,2-dimethoxyethane, methyl acetate, ethyl acetate, nitromethane, 1,3-propane sultone, γ-valerolactone, methyl isobutyryl acetate, 2-methoxyethyl acetate, 2-ethoxyethyl acetate, diethyl oxalate, ionic liquids, and any combination thereof. In some embodiments or examples, the lithium salt may be dissolved in an organic solvent selected from the group consisting of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and any combination thereof.
[0158] The electrolyte may include an additive of one or more alkali metal salts selected from the group consisting of LiPF6 LiBF4, LiAsF6, LiSbF6, LiClO4, LiAlCl4, LiGaCl4, LiC(SO2CF3)3, LiN(SO2CF3)2, LiSCN, LiSO2CF2CF3, LiC6F5SO3, LiO2CCF3, LiSO3F, LiB(C6H5)4, LiCF3SO3, LiNO3, and mixtures thereof. In other embodiments, the additive may be selected from one or more of the following: fluoroethylene carbonate (FEC), vinylethylene carbonate (VEC), ethylene carbonate (VC), propylene carbonate (PC), ethyl methyl carbonate (EMC), propane sultone (PS), and mixtures thereof. Electrolyte additives may further improve certain features of the battery. For example, an electrolyte (e.g., lithium hexafluorophosphate) may include an additive (e.g., fluoroethylene carbonate) dissolved in an organic solvent (e.g., diethyl carbonate).
[0159] In some embodiments or examples, the lithium salt may be dissolved in one or more organic solvents as described above, wherein the one or more organic solvents are present in a volume to volume ratio ranging from 10: 1 to 1: 10. For example, a lithium salt (e.g., 1M LiPF6) may be dissolved in FEC / DEC (2:8) v%, FEC:EMC (3:7) w / w+2wt.%VC, EC / EMC / DEC (3 / 5 / 2vol%)+1wt.%VC+10wt.%FEC, or EC / EMC (3:7) wt.%+1wt.%VC.
[0160] In some embodiments or examples, the separator is used to separate the anode from the cathode and allows the lithium ions in the electrolyte to pass freely. The separator can be selected from a series of different porous polymer films. It should be understood that any porous polymer film with suitable porosity, tortuosity and thickness can be selected as a separator. For example, a separator material based on a polymer film can be selected. In one embodiment or example, the separator can be selected from polyethylene (PE), polypropylene (PP) or polyethylene terephthalate (PET). In another embodiment, a nonwoven fiber material is selected as a separator, and the nonwoven fiber material comprises a fiber selected from nylon, polyethylene terephthalate (PET), cellulose, aramid or polyacrylonitrile.
[0161] In some embodiments or examples, the electrochemical cell may be an energy storage device. The energy storage device may be a battery. For example, the battery may be a secondary battery. In a specific example, the battery may be a lithium-ion battery (Li-ion battery).
[0162] Anode compositions for lithium-ion batteries
[0163] In some embodiments or examples, the present disclosure also provides a method for improving the cycle stability of a battery pack, the battery pack having an anode and a cathode, at least one electrolyte and an optional separator, wherein the anode comprises an anode composition as described herein. It has been found that an anode comprising an anode composition provides a particularly effective anode for a battery pack (e.g., a Li-ion battery pack) capable of maintaining a long-term capacity retention rate. In some embodiments or examples, the discharge capacity of the anode inside the battery pack may be at least about 800 mAh / g within at least 100 cycles of the battery pack. In some embodiments or examples, the specific capacity (mAh / g) may be at least about 500, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400, 2600, 2800, 3000 or 3500. In some embodiments or examples, the specific capacity (mAh / g) may be less than about 3500, 3400, 3200, 3000, 2800, 2600, 2400, 2200, 2000, 1800, 1600, 1400, 1200, 1000, 800, 600 or 500. The specific capacity (mAh / g) may be within the range provided by any two of these upper and / or lower limits. In some embodiments or examples, the number of cycles may be at least 80, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, 400, 420, 440, 460, 480, 500, 1000 or 1500.
[0164] The long-term cycling performance of an electrochemical cell (e.g., Li-ion battery) comprising the anode composition can be tested for high silicon content anodes (i.e., about 70% silicon content) with different capacity limits. According to at least some embodiments or examples as described herein, the initial discharge capacity of the anode comprising the anode composition can be at least about (in mAh / g) 600, 800, 1100, 1200, 1300, 1400, 1500, or 1600. At least according to some embodiments or examples, at least about 80% of the discharge capacity can be retained after 100, 200, 300, 400, 500, 800, 1000, or 1500 cycles.
[0165] It should be understood that constant current charge-discharge cycle experiments can generally be used to evaluate the performance indicators of battery packs: capacity during cycling, rate capacity, coulombic efficiency and capacity retention.
[0166] In some embodiments or examples, the present disclosure also relates to the use of an anode comprising an anode composition as described herein in an electrochemical cell. For example, the electrochemical cell can be an energy storage device, such as a battery, preferably a secondary battery. More specifically, the battery can be a lithium ion battery.
[0167] In some embodiments or examples, the present disclosure also relates to an anode comprising the anode composition, wherein the anode can be a battery anode, more specifically, a lithium-ion battery anode.
[0168] It has been found that the anode composition, which may include or consist of micro silicon active material particles, optionally one or more binders, optionally one or more conductive materials, and optionally one or more additives, significantly reduces the effects shown by SEI formation and silicon expansion and degradation, and thus provides improved Li-ion battery performance. The anode composition provides high first cycle efficiency, as well as the additional advantage of providing controlled silicon utilization, which in turn improves the high current response and performance of the battery. For example, an electrochemical cell (e.g., a Li-ion battery) comprising an anode composition as described herein allows partial utilization / lithiation of silicon, and the specific capacity of the anode is reduced and controlled by the amount of lithium that the anode can supply, thereby providing an improved average coulombic efficiency (CE) of at least about 75%, 80%, 85%, 90%, 95%, 98%, 99% or 99.5% or 99.8% or 99.9% or more or less than 100% within at least 200 cycles. In another example, using the anode composition as an anode provides improved performance of a lithium-ion battery, the improved performance showing cycle stability after at least 200 cycles at C / 2.
[0169] Furthermore, it has been unexpectedly discovered that if the N / P ratio of an anode containing mainly micro-silicon (e.g., >70%) is controlled to a value above 3 (e.g., 3.3), stable cycling of the anode can be provided to achieve more than 200 cycles at a capacity retention of greater than 80%. In other words, a high N / P ratio limits the degree of lithiation of micro-silicon because Li + The amount of silicon is fixed by the cathode when the cell is assembled. This results in a degree of silicon lithiation of about 20% to about 80%, rather than 80% to 90% as seen in conventional cell assemblies where the anode comprises primarily graphite, which has a stabilizing effect on cell performance. It will be appreciated that the anode is significantly oversized relative to the amount of lithium contained in the cell and provided by the cathode. Advantageously, because the degree of lithiation is limited by an oversized anode, the level of expansion of the silicon and its degradation is also limited.
[0170] Preparation method
[0171] In some embodiments or examples, the present disclosure relates to a method for preparing an anode of an electrochemical cell. The method can be used to prepare an anode according to any embodiment or example as described herein. It should be understood that the anode prepared by the method may include an anode composition comprising microsilicon active material particles. It should also be understood that the anode prepared by the method may include an anode composition or consist of an anode composition, the anode composition comprising microsilicon active material particles, optionally one or more additional active materials, optionally one or more binders, optionally one or more conductive materials, optionally one or more additives, and optional solvents. Microsilicon active material particles, one or more additional active materials, one or more optional binders, one or more optional conductive materials, one or more optional additives, and one or more optional solvents can be selected from any one or more of the embodiments or examples as described herein.
[0172] In some embodiments or examples, a method for preparing an anode of an electrochemical cell comprises the following steps: (i) preparing an anode slurry, the anode slurry comprising microsilicon active material particles, optionally one or more additional active materials, optionally one or more binders, optionally one or more conductive materials, optionally one or more additives and a solvent system; and (ii) casting the anode slurry layer onto a current collector material to provide a wet anode composition layer on the current collector material.
[0173] In some embodiments or examples, the method may further comprise step (iii) curing the wet anode layer by solvent evaporation to provide a dry anode composition layer on the current collector material.
[0174] In some embodiments or examples, the solvent may be an organic solvent selected from the following: aromatic compounds, halogenated aromatic compounds, halogenated aliphatic hydrocarbons, aliphatic hydrocarbons, glycols, ethers, glycol ethers, esters, alcohols, ketones, or combinations thereof. In some embodiments or examples, the solvent may be present in an amount between about 40wt.% and 90wt.%, between about 40wt.% and 70wt.%, or between about 40wt.% and 60wt.% (by weight % of the total anode composition). The solvent may be a low boiling point organic solvent, or a mixture of one or more of such solvents. In some embodiments or examples, the solvent may be selected from the group comprising: water, methanol, ethanol, n-propanol, isopropanol, tetrahydrofuran, dichloromethane, chloroform, diethyl ether, room temperature ionic liquids, ethylene glycol, glycerol, formamide, N-methylformamide, dimethylformamide, N-methylsterone, an aqueous solution thereof, and any mixture thereof. For example, the solvent may be water, ethanol, N,N'dimethylformamide, or a combination thereof.
[0175] In some embodiments or examples, the ratio of the binder to the micro-silicon active material particles may be about 1:40, 1:35, 1:32, 1:30, 1:25, 1:23, 1:20, 1:15, 1:10, 1:9, 1:6 or 1:4. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:4 to about 1:32. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:8 to about 1:23. The ratio of the binder to the micro-silicon active material particles may be in the range of about 1:9 to about 1:15.
[0176] In some embodiments or examples, the binder (in wt.%) may be present in the anode composition in a range of about 2.5 to 15. The binder (in wt.%) may be present in the anode composition in an amount less than about 15, 12, 10, 8, 5, or 2.5. The binder (in wt.%) may be present in the anode composition in an amount of at least about 2.5%, 5%, 8%, 10%, 12%, or 15%. The amount of binder (in wt.%) present in the anode composition may be within the range provided by any two of these upper and / or lower limits. For example, the binder (in wt.%) may be present in the anode composition in a range of about 3 to about 8 or about 4 to about 8.
[0177] It has been found that the pH of the binder may affect the electrochemical performance of the anode composition. In some embodiments or examples, the pH of the binder may be less than 9, 8, 7, 6, 5, 4, 3 or 2. In some embodiments or examples, the pH of the binder may be at least 2, 3, 4, 5, 6, 7, 8 or 9. The pH of the binder may be within the range provided by any two of these upper and / or lower limits. For example, the pH of the binder may be in the range of 4 to 8. Preferably, a binder pH of less than 7 may be beneficial to the electrochemical performance of the micro-silicon anode, and may be due to (i) reduced corrosion of pure silicon in acidic regions and / or (ii) greater affinity of silicon to interact with the binder, such as PAA.
[0178] In some embodiments or examples, the viscosity of the anode slurry may be in the range of about 10 mPas to 100,000 mPas. The viscosity (mPas) may be less than about 100,000, 90,000, 80,000, 70,000, 60,000, 50,000, 40,000, 30,000, 20,000, 10,000, 8000, 6000, 4000, 2000, 1000, 800, 600, 400, 200, 100, 50 or 10. The viscosity can be at least about 10, 20, 40, 60, 80, 100, 300, 500, 700, 900, 1000, 3000, 5000, 7000, 9000, 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000 or 100,000. The viscosity (mPas) of the anode slurry can be in the range provided by any two of these upper limits and / or lower limits. For example, the viscosity (mPas) of the anode slurry can be in the range of about 2500mPas to about 8000mPas. All viscosity values described herein can be at a given shear rate. In an embodiment, the shear rate can be the shear rate used in any recognized standard test method in the art.
[0179] In some embodiments or examples, the thickness of the dry anode composition may be in the range of about 5 μm to about 45 μm. The thickness (μm) of the dry anode composition may be less than about 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 8, 6, or 5. The thickness (μm) of the dry anode composition may be at least about 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or 70. The thickness (μm) of the dry anode composition may be within the range provided by any two of these upper and / or lower limits.
[0180] In some embodiments or examples, in step (iii)(a), the wet anode composition layer may be maintained at a temperature of about 40°C to about 60°C for about 30 seconds to about 5 minutes. The wet anode composition may be maintained at a temperature (°C) of less than about 60, 55, 50, 45 or 40. The wet anode composition may be maintained at a temperature (°C) of at least about 40, 45, 50, 55 or 60. The wet anode composition may be maintained at a temperature (°C) within the range provided by any two of these upper and / or lower limits. The wet anode composition may be maintained at a temperature as described herein for less than about 24 hours, 12 hours, 8 hours, 4 hours, 2 hours, 1 hour, 30 minutes, 5 minutes, 4 minutes, 3 minutes, 2 minutes, 1 minute or 30 seconds. The wet anode composition may be maintained at a temperature as described herein for at least about 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 10 hours, 12 hours or 24 hours. The wet anode composition can be maintained at a temperature as described herein for a time within a range provided by any two of these upper and / or lower limits.
[0181] In some embodiments or examples, in step (iii)(b), the wet anode composition may be maintained at a temperature between about 90° C. and about 180° C. for about 30 seconds to about 5 minutes. The wet anode composition may be maintained at a temperature (° C.) of less than about 180, 170, 160, 150, 140, 130, 120, 115, 110, 105, 100, 95, or 90. The wet anode composition may be maintained at a temperature (° C.) of at least about 90, 95, 100, 105, 110, 115, 120, 130, 140, 150, 160, 170, or 180. The wet anode composition may be maintained at a temperature (° C.) within the range provided by any two of these upper and / or lower limits. The wet anode composition may be maintained at a temperature as described herein for less than about 24 hours, 12 hours, 8 hours, 4 hours, 2 hours, 1 hour, 30 minutes, 5 minutes, 4 minutes, 3 minutes, 2 minutes, 1 minute, or 30 seconds. The wet anode composition may be maintained at a temperature as described herein for at least about 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 10 hours, 12 hours, or 24 hours. The wet anode composition may be maintained at a temperature as described herein for a time within the range provided by any two of these upper and / or lower limits.
[0182] In some embodiments or examples, the anode slurry may be made homogenous to provide additional advantages / improvements.
[0183] In some embodiments or examples, the present disclosure relates to a method for assembling an electrochemical cell, wherein the method may include the following steps: preparing an anode as defined by at least the method according to any one of the examples described herein, wherein the anode may include an anode composition, the anode composition including microsilicon active material particles; and assembling the anode into an electrochemical cell. In some other embodiments or examples, the present disclosure relates to a method for assembling an electrochemical cell, wherein the method may include the following steps: preparing an anode as defined by at least the method according to any one of the examples described herein, wherein the anode may include or consist of an anode composition according to at least any one of the examples described herein, the anode composition including microsilicon active material particles, optionally one or more additional active materials, optionally one or more binders, and optionally one or more conductive materials, at least according to any one of the examples described herein; and assembling the anode into an electrochemical cell.
[0184] When forming the anode slurry, some or all of the solvent may be removed (eg, by natural evaporation, forced evaporation, or under vacuum) to produce a solid or viscous anode slurry.The anode slurry may be formed or molded into any desired shape, such as an anode.
[0185] In some embodiments or examples, the anode slurry may also be deposited on a current collector material as defined herein to produce an anode. It should be understood that the anode is a combination of a current collector material and an anode composition, also referred to as an anode composition applied to a current collector material. The current collector material may be selected from any current collector material mentioned herein.
[0186] During the preparation of the anode, the anode composition can be applied to only a portion of the surface of the current collector material. In some embodiments or examples, the portion (%) may be less than about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 or 5. In some embodiments or examples, the anode composition can be applied to the current collector material by casting (e.g., roll-to-roll processing).
[0187] Those skilled in the art will appreciate that numerous changes and / or modifications may be made to the above-described embodiments without departing from the broad general scope of the present disclosure. Therefore, the embodiments of the present invention should be considered in all aspects as illustrative and not restrictive.
[0188] Example
[0189] The present disclosure is further described by the following embodiments. It should be understood that the following description is only for the purpose of describing specific embodiments and is not intended to limit the above description.
[0190] Example 1: General procedure for preparing anodes
[0191] Various commercially available silicon materials can be used to prepare the anode composition, as described herein and further exemplified in the Examples. Examples of a selected number of properties of such silicon materials are given in Table 1 below, including their PSD, BET surface area, and measured impurities (measured via ICP-AES).
[0192] Table 1: Elkem 2 Silicon Material Properties
[0193]
[0194] It is understood that impurities may be present in the silicon material, one such example being shown above in Table 1. Such impurities may be present in the micro silicon active material particles, preferably in an amount less than about 3000 ppm total impurities.
[0195] To prepare the anode slurry, the binder solution and the conductive material are combined using a planetary centrifugal mixer. The mixture is then combined at 2000 rpm for 2 minutes, manually mixed with a spatula, and then mixed for another 2 minutes. Microsilicon active material particles and the required amount of additional water are added and the mixing step is repeated. Active graphite is added and the mixing step is repeated. Unless otherwise stated, a predetermined amount of anode slurry is transferred to a container compatible with the Dispermat and mixed for 5 minutes at 6000 rpm using an overhead mixer (e.g., VMA-Getzmann Dispermat).
[0196] In the full cell assembly, the slurry was cast onto copper foil and dried at 60°C and then cut for button cell assembly. The electrodes (coated anode and commercially available NCM 523 cathode) were further dried at 110°C under vacuum for 12 hours. 150 μL electrolyte (e.g., FEC / DEC (2:8) vol. %) containing 1M LiPF6 and a separator (e.g., Whatman glass fiber) were used for button cell (CR 20232 type) assembly. For the charge / discharge cycle test, the button cell was activated at 0.05C for 1 cycle and then cycled at 0.5C for long-term stability testing. The C rate is based on the mass of active materials (Si particles, graphite) in the electrode. The voltage range of the charge / discharge test was 4.2-2.5V during formation and 4.2-3V during cycling. The charge / discharge test was performed on a Neware multi-channel battery tester controlled by a computer. Four replicate batteries were prepared and tested for each condition.
[0197] In the half-cell assembly, the slurry was cast onto copper foil and dried at 60°C, then cut for button cell assembly. The electrode was further dried at 110°C under vacuum for 12 hours. Lithium (Li) metal was used as the counter electrode. 150 μL electrolyte (e.g., FEC / DEC (2:8) vol. %) containing 1M LiPF6) and a separator (e.g., Celgard 2500) were used for button cell (CR 2032 type) assembly. For the charge / discharge cycle test, the button cell was activated at 0.05C for 1 cycle, then activated at 0.1C for two cycles, and then cycled at 0.5C for long-term stability testing. The C rate is based on the mass of the active material (Si particles, graphite) in the electrode. The voltage range of the charge / discharge test was 0.005-1.50V relative to Li. The charge / discharge test was performed on a Neware multi-channel battery tester controlled by a computer. Four replicate batteries were prepared and tested for each condition.
[0198] Example 2: Surface area and particle size studies
[0199] Example 2 (a) Sample containing microsilicon
[0200] Each silicon material was tested using a micro-silicon anode composition as described in Example 1, wherein the micro-silicon active material particle content was about 70%.
[0201] It should be understood that one (1) battery slurry was produced per microsilicon sample.
[0202] For each silicon anode configuration assembled:
[0203] a. Four (4) coin cells (relative to lithium metal)
[0204] b. Four (4) full coin cells (with commercial grade NCM 523 cathode)
[0205] i. Testing under full battery design with limited capacity
[0206] ii. The capacity of the anode in a full cell is limited to 30% to 36%
[0207] In the 30% to 36% limited capacity test setup, all micro-silicon containing anodes were paired with NCM 523 cathodes. The 30% to 36% capacity limit refers to the extent to which the anode is utilized. In practice, this means that the anode area capacity is too large compared to the cathode. Considering that the cathode contains the lithium raw material for the battery when the cell is assembled, the area capacity of the two electrodes is selected so that only a maximum of 30% to 36% anode lithiation is possible on the first charge.
[0208] Example 2 (b) Specific coating capacity - anode
[0209] The specific coating capacity of the anode is calculated by dividing the total cell per cm 2 The capacity delivered by the cathode is divided by g / cm 2 The cyclic capacity values obtained at C / 2 (start of 2nd cycle) rate for all anode configurations fall within the target range of 600 to 700 mAh / g. Figure 1a A full battery is shown.
[0210] Example 2 (c) Specific coating capacity - cathode
[0211] The specific coating capacity of the cathode is calculated by dividing the total cell per cm 2 The capacity delivered by the cathode is divided by g / cm 2 The values obtained for all anode configurations fell within the target range of 160 to 165 mAh / g. This capacity figure was expected given the NCM 523 cathode material used.
[0212] Example 2 (d) Electrode composition
[0213] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used for all experiments in Example 2 are shown in Table 2 below.
[0214] Table 2: Electrode composition
[0215]
[0216] Example 2 (e) Slurry preparation
[0217] The material amounts specified in Table 2 were used for the slurry preparation process for Elkem 1, 2, 3 and 4 microsilica materials. The slurries were prepared using the procedure in Example 1.
[0218] Example 2.1 Surface area and particle size study: full cell testing
[0219] Example 2.1 (a) Full cell test setup
[0220] The electrochemical testing setup for the full cells was as described in Example 1. The testing procedure is detailed in Table 3 below.
[0221] Table 3: Full cell formation test procedure
[0222] name magnification Cut-off(V) Notes still 1 hour Tap Charging C / 3 3 still 12 hours Constant current and constant voltage charging C / 20 4.2 Cut-off current (C / 100) Constant current discharge C / 20 2.5 Final loop
[0223] The current density used for the cycling tests was based on the electrode capacity obtained from the final delithiation step of the formation procedure.
[0224] Table 4: Cycling test procedure for full cells
[0225] name magnification Cut-off(V) Notes Constant current and constant voltage charging C / 2 4.2 Cut-off current (C / 20) Constant current discharge C / 2 3 Repeat from step 1 Repeat until battery fails or capacity < 80% Final loop
[0226] Example 2.1(b) Summary of key findings from full battery testing
[0227] Elkem 1, 2, and 3 silicon materials showed superior electrochemical performance, resulting in >89% ICE and higher capacity retention compared to Elkem 4. At 95.3% capacity retention, Elkem 2 showed 24 more cycles compared to Elkem 1, 29 more cycles compared to Elkem 3, and 131 more cycles compared to Elkem 4.
[0228] Reducing SSA has improved the electrochemical behavior by increasing ICE and extending the cycle life of Si anodes.
[0229] A summary of the limited capacity full cell electrochemical data is shown in Table 5 below.
[0230] Table 5: Summary of electrochemical data for limited capacity full cells
[0231]
[0232] The following table provides the D50 particle size, BET surface area and D 50 Ratio of the surface area to the BET surface area.
[0233] Table 6: Summary of key findings from full battery testing
[0234]
[0235] D in Table 6 50 Particle size, BET surface area and D 50 The range of the ratio between particle size and BET surface area is defined as a representative range of the measurements obtained.
[0236] Compared with the higher (6.0-8.0μm) and lower (0.1-3.0μm) D 50 Particle size and high BET surface area (>3.5m 2 / g) The D generated by both 50 The particle size to BET surface area ratios were higher (3.5-6.0) or lower (0.01-1.0) from 3.0 to 6.0 μmD. 50 Particle size and 1.0 to 3.5m 2 The BET surface area range of D 50 Silicon materials having a particle size to BET surface area ratio of 1.0 to 3.5 exhibit excellent cycle life.
[0237] Example 2.2 Surface area and particle size study: half-cell test
[0238] Example 2.2 (a) Test setup for half-cell testing
[0239] The electrochemical test setup for the half-cells was as described in Example 1. The test procedure is detailed in Table 7 below.
[0240] Table 7: Half-cell formation test procedure
[0241]
[0242] The current density used for the cycling tests was based on the electrode capacity obtained from the final delithiation step of the formation procedure.
[0243] Table 8: Cyclic test procedure for half cells
[0244]
[0245] Example 2.2(b) Summary of key findings from half-cell testing
[0246] All half-cells were tested under fully lithiated conditions. Figure 2 It is shown that the cycling stability of various silicon samples is determined by their respective particle size, surface area, and the ratio between particle size and surface area. 50 Particle size and 1.0 to 3.5m 2 / g BET surface area 50 The samples with particle size to BET surface area ratios of 1.0 to 3.5 showed the fastest capacity degradation. 50 Particle size and 35 to 50m 2 / g BET surface area 50 Samples with a particle size to BET surface area ratio of 0.01 to 0.1 showed the most stable cycling performance. In half-cell tests with unlimited lithium supply, small particle size and large surface area did not negatively affect the cycling performance.
[0247] The following table provides the microsilicon active material D 50 Particle size, BET surface area, D 50 Summary of the ratio of particle size to BET surface area and the corresponding electrochemical data of half-cell measurements.
[0248] Table 9: Summary of key findings from half-cell testing
[0249]
[0250] Example 3 Capacity Limitation Levels 30%, 50% and Full Capacity
[0251] Each micro-silicon-containing anode was paired with an NCM 523 cathode in 30%, 50% and full capacity test settings. The degree of capacity limitation refers to the degree to which the anode is utilized. In practice, this means that the anode area capacity is too large compared to the cathode. Considering that the cathode contains the lithium raw material of the battery when the battery is assembled, the area capacity of the two electrodes is selected so that only the maximum capacity converted to the selected anode lithiation degree is utilized during the first charge.
[0252] Example 3 (a) Electrode composition
[0253] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used for all experiments are shown in Table 10 below.
[0254] Table 10: Electrode composition
[0255] Material describe Content [wt. %] Active Materials Elkem 2 70 Conductive filler Timrex KS6L Flake Graphite 20 Conductive additives Timcal Super C65 2 Adhesives PAA 25%, neutralized with LiOH 8
[0256] Example 3 (b) Slurry preparation
[0257] First, polyacrylic acid (18.20 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.91 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (24.20 g) and microsilica (31.85 g) were then added and the mixing steps were repeated. Finally, flake graphite (9.10 g) was added and the mixing steps were repeated. 64.81 g of this complete mixture was transferred to a container compatible with Dispermat and mixed at 6000 rpm for 5 minutes.
[0258] Example 3(c) Electrochemical Testing Procedure
[0259] Full cells were assembled using the procedure described in Example 1. The cycling procedures are shown in Tables 3 and 4 above.
[0260] Example 3.2(d) Cycle Testing - Summary of Key Findings
[0261] Increasing the capacity limit increases the stress on the tested anode compositions in the full cell, with ICE increasing with higher capacity utilization and capacity retention decreasing. At 99% capacity limit, ICE is 0.4% higher than at 35% capacity limit (Table 11). Limiting the capacity to 35%, the cycle life is extended by more than 258 cycles to reach the same level of capacity retention as at 99% capacity limit (Figure 3). At 50% capacity limit, ICE is only 0.3% less than at 99% capacity limit, but capacity retention is still poor, with 20% of capacity lost after 138 cycles.
[0262] Table 11: Summary of electrochemical data for limited capacity full cells
[0263]
[0264] Example 4 Pre-lithiation of Micro-Si Anode
[0265] Example 4.1 Electrochemical pre-lithiation
[0266] Example 4.1 (a) Electrode composition
[0267] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used for all experiments are shown in Table 12 below.
[0268] Table 12: Electrode composition
[0269] Material describe Content [wt%] Active Materials Elkem 2 70 Conductive filler Timrex KS6L Flake Graphite 20 Conductive additives Timcal Super C65 2 Adhesives PAA 25%, neutralized with LiOH 8
[0270] Example 4.1 (b) Slurry preparation :
[0271] First, polyacrylic acid (18.20 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.91 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (24.20 g) and microsilica (31.85 g) were then added and the mixing steps were repeated. Finally, flake graphite (9.10 g) was added and the mixing steps were repeated. 64.81 g of this complete mixture was transferred to a container compatible with Dispermat and mixed at 6000 rpm for 5 minutes.
[0272] Example 4.1 (c) Pre-lithiation step
[0273] The electrochemical test program was set up as follows:
[0274] • Cycle 1 in half-cell setup: Partial formation cycle based on the anode expected capacity reaching a certain % at C / 20.
[0275] • The first lithiation is limited by capacity (mAh / g) to a maximum of 30% or 20% of the expected capacity of the anode (accounting for the ~10% lithium loss in the first cycle).
[0276] Table 13: Half-cell formation test procedure (with pre-lithiation)
[0277] name magnification Cut-off(V) Notes still 12 hours Constant current discharge C / 20 0.01 Capacity cutoff value (pre-lithiation degree % * anode expected capacity mAh Final loop
[0278] The slurry was cast onto copper foil and dried at 60°C and then cut for button cell assembly. The electrodes were further dried at 110°C under vacuum for 12 hours. Lithium (Li) metal was used as the relative electrode and a Celgard separator was used. 150 μL of FEC / DEC (2:8) vol.% containing 1M LiPF6 was used as the electrolyte for the button cell assembly. The button cell was lithiated at 0.05C for 1 cycle and stopped when the capacity reached the desired pre-lithiation degree. The C rate is based on the mass of the active material (Si particles, graphite) in the electrode. Two replicate cells were prepared and tested for each condition.
[0279] Example 4.1 (d) Post-prelithiation steps
[0280] The button cell was taken out and introduced into a glove box (under Ar atmosphere) and disassembled to prepare a full cell. Prior to assembly, the anode was washed with DMC and dried. The full cell was assembled using the procedure described in Example 1. For the cycling procedure, see Tables 3 and 4.
[0281] Example 4.1(e) Cycle Testing—Summary of Key Findings
[0282] Pre-lithiated and unlithiated full cells were compared using similar capacity limits. The initial Coulombic efficiency increased by 1% from 89% to 90% on average.
[0283] The cycling capacity and average Coulombic efficiency increased significantly. Negligible capacity loss was observed in the first 330 cycles. The 20% lithium reservoir achieved 95% capacity retention at 260 cycles and 80% retention after 680 cycles (Figure 4).
[0284] Table 14: Summary of electrochemical data for pre-lithiation and limited capacity full cells
[0285]
[0286] Example 4.2 Direct contact pre-lithiation
[0287] Example 4.2 (a) Electrode composition
[0288] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used for all experiments are shown in Table 15 below.
[0289] Table 15: Electrode composition
[0290] Material describe Content [wt%] Active Materials Elkem 2 70 Conductive filler Timrex KS6L Flake Graphite 20 Conductive additives Timcal Super C65 1.95 Conductive additives Carbon Nanotubes 0.05 Adhesives PAA, 25, neutralized with LiOH 8
[0291] Example 4.2 (b) Slurry preparation :
[0292] First, polyacrylic acid (19.24 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.94 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (14.91 g) and microsilica (33.67 g) were then added and the mixing step was repeated. Next, flake graphite (9.62 g) was added and the mixing step was repeated. Finally, the pre-dispersed carbon nanotube solution (6.01 g) was added and the mixing step was repeated. 60.31 g of this complete mixture was transferred to a container compatible with the Dispermat and mixed at 6000 rpm for 5 minutes.
[0293] Example 4.2 (c) Pre-lithiation step and electrochemical testing procedure
[0294] Direct contact experimental setup:
[0295] Table 16: Direct contact pre-lithiation time and added weight
[0296]
[0297] The slurry was cast onto copper foil and dried at 60°C and then cut for button cell assembly. The electrodes (coated anode and commercially available NCM 523) were further dried at 110°C under vacuum for 12 hours. The electrodes were then introduced into an Ar glove box where a pre-lithiation process was performed. The silicon anode was in direct contact with the lithium foil for a specific time (Table 16) with an electrolyte medium (2.0 ml of FEC / DEC 2:8 V% containing 1M LiPF6) in between. Pressure (certain weight) was applied to establish direct contact between the silicon and the lithium foil (Table 16), thereby starting the pre-lithiation process. The pre-lithiation process results and the degree of pre-lithiation depend on the contact duration, the pressure applied, and the uniformity of the contact.
[0298] Based on thermodynamics, lithium metal foil will spontaneously react with silicon (Si) to form a Li-Si alloy as follows:
[0299] Net reaction 4.4Li+Si=Li 4.4 Si
[0300] Reduction 4.4Li+Si+4.4e-=Li 4.4 Si
[0301] Oxidation 4.4Li-4.4e-=4.4Li+
[0302] ΔG=-nEF~-4.4*96500=-42kJ mol -1
[0303] Where ΔG is the Gibbs free energy of the overall reaction, E is the potential of the overall reaction, and F is the Faraday constant. Based on experimental data, E is assumed to be about 0.1 V.
[0304] The pre-lithiated electrodes were then assembled into full cells using the procedure described in Example 1. See Tables 3 and 4 for the cycling procedure.
[0305] Example 4.2(d) Cycle Testing—Summary of Key Findings
[0306] Direct contact pre-lithiation increases the ICE of each electrode compared to the control. The achievable lithiation percentage is a function of the contact time and the applied pressure. Table 17 shows the capacity retention of the battery at cycle 90, where 200 g / 5 min and 100 g / 5 min (pressure / time) have the same capacity retention (98.9%), and the best performing samples 200 g / 10 min and 100 g / 15 min also have the same capacity retention (101%). Clearly, the degree of pre-lithiation can be controlled by controlling the contact time and applied pressure.
[0307] Table 17: Summary of electrochemical data for limited capacity full cells
[0308]
[0309] Example 5 Micro-Si anode with CMC / SBR binder at 30% capacity limit
[0310] 5(a) Electrode composition
[0311] The specific electrode compositions used for this experiment are shown in Table 18 below.
[0312] Table 18: Electrode composition
[0313]
[0314] Example 5 (b) Slurry preparation
[0315] Example 5(b)(i) - 4% CMC, 4% SBR
[0316] First, carboxymethyl cellulose binder (52.00g, CMC) and conductive carbon black Super C65 (0.52g) are merged using Thinky Mixer ARE-250 CE planetary mixer. The mixture is incorporated at 2000rpm for 2 minutes, and then repeated for 2 minutes. Manual mixing with a spatula is required in the middle. Water (18.30g) and microsilicon (18.20g) are subsequently added, and the mixing step is repeated. Next, flake graphite (5.20g) is added and the mixing step is repeated. Finally, styrene-butadiene rubber (2.08, SBR) is added and mixed for 2 minutes at 900rpm, and then repeated for 2 minutes. Manual mixing with a spatula is required in the middle. 72.47g of this complete mixture is transferred to a container compatible with Dispermat, and mixed for 5 minutes at 900rpm.
[0317] Example 5(b)(ii) - 8% LiPAA
[0318] First, polyacrylic acid (18.20 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.91 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (19.25 g) and microsilica (31.85 g) were then added and the mixing steps were repeated. Finally, flake graphite (9.10 g) was added and the mixing steps were repeated. 61.01 g of this complete mixture was transferred to a container compatible with Dispermat and mixed at 3000 rpm. Additional water (3.81 g) was added dropwise to the mixture and the mixing speed was increased to 6000 rpm for 5 minutes.
[0319] Example 5 (c) Electrochemical Testing Procedure
[0320] Full cells were assembled using the procedure described in Example 1. The cycling program is as shown in Tables 3 and 4 above.
[0321] Example 5(d) Cyclic Testing - Summary of Key Findings
[0322] Table 19: Summary of electrochemical data for limited capacity full cells
[0323]
[0324] The full cell results using 8% PAA binder were used to compare the effect of the binder on the electrochemical performance of the 70% micro-Si anode. Using CMC / SBR binder improved ICE by 0.6% compared to PAA binder. However, the CMC / SBR full cell lost 20% of its capacity after only about 155 cycles, while the PAA full cell lost the same amount of capacity after 277 cycles (Figure 5).
[0325] Example 6 Effect of Binder / Binder pH
[0326] The degree of neutralization of PAA with LiOH, and therefore the pH of the resulting binder, showed a direct impact on the electrochemical performance of the micro-silicon anode. It was found that the binder results with a pH between 4 and 5 were particularly beneficial, thereby improving the capacity retention while requiring less conductive additives to further enhance the electrode performance. When the pH of the PAA binder was above 7, the capacity retention of the micro-silicon anode dropped significantly. The high binder pH also resulted in the need for higher amounts of conductive additives.
[0327] The gradual decrease in electrochemical performance of the micro-Si anode at a pH close to 7 or higher may be caused by Si oxidation caused by exposure of Si particles to LiOH. In addition, the reduced number of -COOH groups at pH above 7 can reduce the degree of esterification of silane alkoxy groups on the surface of Si particles, which enables the formation of strong bonds between the polymer chain and Si. This will make the PAA binder less effective in offsetting the effect of volume changes of Si particles in the electrode matrix. In addition, the difference in solid content to achieve processable slurry viscosity based on the binder pH may affect the micro-Si anode morphology, further contributing to the changes in electrochemical performance.
[0328] Example 6.1 Comparison of 25% vs. 95% Neutralized PAA with and without CNTs
[0329] Example 6.1 (a) Electrode composition
[0330] An anode composition consisting of 70% Elkem 2 microsilicon was produced. Table 20 below shows the specific electrode compositions used for all experiments in Example 6.1.
[0331] Table 20: Electrode / slurry composition
[0332]
[0333] Example 6.1 (b) Slurry preparation
[0334] The material composition described in Table 20 was used for slurry preparation.
[0335] The slurry without carbon nanotubes was prepared using the procedure described in Example 1. 0.95Slurry of PAA binder, omitting the final mixing step using Dispermat.
[0336] The procedure described in Example 4.2(b) was used to prepare 0.25 PAA and Li 0.95 Carbon nanotube-infused slurry of PAA binder system.
[0337] Example 6.1 (c) Full Cell Test Setup
[0338] Full cells were assembled using the procedure described in Example 1. The cycling program is as shown in Tables 3 and 4 above.
[0339] Example 6.1(d) Cycling Tests - Summary of Key Findings from Full Cell Testing
[0340] Overall, the addition of CNTs improved ICE and extended cycle life. In the case of 25% neutralized PAA [Li0.25PAA], the addition of 0.05wt% CNTs increased the cycle life by 80 cycles compared to 0% CNTs. For the 95% neutralized PAA [Li0.95PAA] example, the addition of CNTs slightly increased ICE, but the capacity retention decreased by 26 cycles ( Figure 6b ). Based on electrochemical testing, Li0.25PAA produced better cycling results than the Li0.95PAA binder system.
[0341] Table 21: Summary of key findings from full battery testing
[0342]
[0343] Table 22: Summary of electrochemical data for limited capacity full cells
[0344]
[0345] In addition, the micro-Si electrode produced by the anode formulation composed of 95% neutralized PAA binder showed a relatively loosely packed morphology, which is more susceptible to particle disintegration and thus electrical isolation during cycling resulting in poor capacity retention. In contrast, a relatively densely packed electrode morphology was produced by the anode formulation composed of 25% neutralized PAA binder, indicating that it is less likely to experience capacity loss due to electrical isolation of Si particles.
[0346] Example 6.2 70% Micro-Si and PAA-copolymer (hydrophilic part) adhesive
[0347] Example 6.2 (a) Electrode composition
[0348] The specific electrode compositions used for all experiments are shown in Table 23 below.
[0349] Table 23: Electrode composition
[0350] Material describe Content [wt%] Active Materials Elkem 2 70 Conductive filler Timrex KS6L Flake Graphite 20 Conductive additives Timcal Super C65 2 Adhesives PAA-copolymer (hydrophilic part) 8
[0351] Example 6.3 (b) Slurry preparation
[0352] PAA copolymer (37.14 g, 9.8 wt.% solution) with hydrophilic part and conductive carbon black Super C65 (0.91 g, Nanografi, Turkey) were combined using a Thinky Mixer ARE-250 CE (Thinky Corp, USA) centrifugal planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (18.05 g) and microsilicon (31.85 g) were then added and the mixing steps were repeated. Finally, flake graphite (9.10 g, KS6L, Imerys, Malaysia) was added and the mixing steps were repeated. 74.65 g of this complete mixture was transferred to a container compatible with Dispermat and mixed at 3000 rpm using an overhead mixer (VMA-Getzmann Dispermat, Germany). 3.81 g of water was added dropwise (1-2 drops / second) to the mixture. The speed was increased to 6000 rpm and allowed to mix for 5 minutes.
[0353] Example 6.2 (c) Electrochemical Testing Procedure
[0354] Full cells were assembled using the procedure described in Example 1. The cycling program is as shown in Tables 3 and 4 above.
[0355] Example 6.2(d) Cycle Testing - Summary of Key Findings
[0356] Table 24: Summary of electrochemical data of limited capacity full cells of micro-Si and PAA-copolymer (hydrophilic part) binder
[0357]
[0358] At a rate of C / 20, the use of PAA copolymer (hydrophilic portion) binder showed an ICE of 90.3% and a discharge capacity of 165 mAh / g based on the weight of the cathode coating and 1357 mAh / g based on the weight of the anode coating. Figure 7a The capacity retention at 60% capacity limit for cycling of the 8% hydrophilic PAA copolymer is shown, where the full cell loses 20% of the cycling capacity after approximately 116 cycles. Figure 7b The initial discharge capacity of the anode shown was 1357 mAh / g, and after about 170 cycles, the capacity dropped to 760 mAh / g.
[0359] Example 7: 70wt% vs. 90wt% Micro-Si Anode Design
[0360] The silicon-dominant anode design is able to achieve high energy density compared to prior art commercial anode formulations containing silicon as an additive material. While the 70wt% micro-silicon anode design is already a silicon-dominant system, further increasing the silicon content to 90wt% will reduce the degree of silicon utilization required to achieve the same capacity as the 70wt% micro-silicon anode design.
[0361] For example, if a 70wt% micro-Si anode design can deliver 800mAh / g coating capacity at a 30% capacity limit, a 90wt% micro-Si anode design can achieve 1000mAh / g at the same capacity limit. This will enable the design of a faster Li + Thinner electrodes with improved ion diffusion capabilities pave the way for new lightweight battery design possibilities. In addition, 90wt% micro-silicon anode design can further increase energy density and support high rate capacity.
[0362] Example 7 (a) Electrode composition
[0363] Anode compositions consisting of 70% and 90% Elkem 2 microsilica were produced. The specific electrode compositions used for all experiments are shown in Table 25 below.
[0364] Table 25: Electrode / slurry composition
[0365]
[0366] Example 7 (b) Slurry preparation
[0367] The slurries were prepared using the compositions in Table 25. The procedure described in Example 4.2(b) was used for the slurry preparation process.
[0368] Example 7 (c) Full Cell Test Cell Setup
[0369] Full cells were assembled using the procedure described in Example 1. See Tables 3 and 4 for the cycling procedure.
[0370] Example 7(d) Cycling Testing - Summary of Key Findings from Full Cell Testing
[0371] The effect of mSi content (70 and 90%) was examined (Figure 8). They have similar starting capacities, but the ICE of the 90% mSi anode is about 1% higher than that of the 70% mSi anode. The 70% mSi anode shows better capacity retention than the 90% mSi system, with 80% capacity retention achieved after 300 cycles, about 77 cycles higher than the capacity retention of the 90% mSi anode.
[0372] Table 26: Summary of electrochemical data for limited capacity full cells
[0373]
[0374] Example 8 Effect of Carbon Nanotube Conductive Additives
[0375] It was found that CNTs improved the conductivity of LIB electrodes when used as a conductive additive, which also provided an effective conductive network for the Si anode. Physical mixing is a simple and effective way to improve the conductivity of Si-based anodes, with the disadvantage of low uniformity and therefore lack of consistency in cycling performance. It was found that the use of CNTs during physical mixing affects the slurry viscosity without directly affecting the slurry processability and anode structure. Fortunately, many advantages were observed after adding CNTs to the anode composition. It was concluded that conductivity and charge transfer were improved by reducing resistance, and based on cycle testing, the life cycle has been extended by about 90 cycles.
[0376] Example 8 (a) Electrode composition (0% CNT)
[0377] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used are shown in Table 27 below.
[0378] Table 27: Electrode composition
[0379] Material describe Content [wt%] Active Materials Elkem 2 70 Conductive filler Timrex KS6L Flake Graphite 20 Conductive additives Timcal Super C65 2 Adhesives PAA 25%, neutralized with LiOH 8
[0380] Example 8 (b) Slurry preparation
[0381] First, polyacrylic acid (18.20 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.91 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (19.25 g) and microsilica (31.85 g) were then added and the mixing steps were repeated. Finally, flake graphite (9.10 g) was added and the mixing steps were repeated. 61.01 g of this complete mixture was transferred to a container compatible with the Dispermat and mixed at 3000 rpm using an overhead mixer (VMA-Getzmann Dispermat). 3.81 g of water was added dropwise (1-2 drops / second) to the mixture. The speed was increased to 6000 rpm and allowed to mix for 5 minutes.
[0382] Example 8 (c) Electrode composition (0.05% CNT)
[0383] An anode composition consisting of 70% micro-silicon was produced. The specific electrode compositions used for all experiments are shown in Table 28 below.
[0384] Table 28: Electrode composition
[0385]
[0386] Example 8 (d) Slurry preparation
[0387] First, polyacrylic acid (18.20 g) (PAA, 250 kDa, 25% neutralized) and conductive carbon black Super C65 (0.89 g) were combined using a Thinky Mixer ARE-250 CE planetary mixer. The mixture was incorporated at 2000 rpm for 2 minutes and then repeated for another 2 minutes. Manual mixing with a spatula was required in the middle. Water (18.53 g) and microsilica (31.85 g) were then added and the mixing step was repeated. Next, flake graphite (9.10 g) was added and the mixing step was repeated. Finally, a pre-dispersed carbon nanotube (CNT) solution (5.69 g) was added and the mixing step was repeated. 60.46 g of this complete mixture was transferred to a container compatible with the Dispermat and mixed at 6000 rpm for 5 minutes.
[0388] Example 8 (e) Electrochemical Testing Procedure
[0389] Full cells were assembled using the procedure described in Example 1. The cycling schedule is shown in Tables 3 and 4.
[0390] Example 8(f) Cyclic Testing - Summary of Key Findings
[0391] The effect of carbon nanotube addition on 70 wt % mSi anode was examined and it was found that 0.05 wt % carbon nanotubes increased ICE by 0.3% and extended cycle life by 85 cycles at 80% capacity retention compared to 0% carbon nanotubes ( FIG. 9 ).
[0392] Table 29: Summary of electrochemical data for limited capacity full cells
[0393]
Claims
1. An anode composition comprising micro-silicon active material particles, The microsilicon active material particles have one or more of the following: (i) a BET surface area of about 0.1 m 2 / g and about 10m 2 / g; (ii) D 50 The particle size is between about 0.1 μm and about 10 μm; and (iii) D 50 The ratio of the BET surface area is between about 0.1 and about 10, and Wherein the amount of the micro-silicon active material particles present in the anode composition is between about 60 wt. % and about 95 wt. % based on the total weight % of the anode composition.
2. The anode composition of claim 1, wherein the amount of the micro-silicon active material particles present in the anode composition is between about 70 wt. % and about 95 wt. %, based on the total weight % of the anode composition.
3. The anode composition according to claim 1 or claim 2, wherein the tap density of the micro-silicon active material particles is between about 0.5 g / cm 2 About 1.5g / cm 2 between.
4. Anode composition according to any one of the preceding claims, wherein the purity of the microsilica active material particles (without oxygen) is at least 95 wt.%, preferably 98 wt.%.
5. The anode composition according to any one of the preceding claims, wherein the D of the micro-silicon active material particles is 50 The particle size is between about 2 μm and about 8 μm.
6. The anode composition according to any one of the preceding claims, wherein the measured BET surface area of the microsilicon active material particles is between about 1 m 2 / g and about 5m 2 / g.
7. The anode composition according to any one of the preceding claims, wherein the D of the micro-silicon active material particles is 50 The ratio of the BET surface area is between about 0.1 and about 6.
8. The anode composition according to any of the preceding claims, wherein impurities selected from the group consisting of Al, Ca, Fe, Ti, P, Cu, Cr, K, V, Ni and Na are present in the microsilica active material particles in an amount of less than about 5000 ppm, either individually or as a total impurity level.
9. The anode composition of any one of the preceding claims, wherein the anode composition further comprises one or more binders.
10. The anode composition of claim 9, wherein the binder is present in the anode composition in an amount ranging from about 2.5 wt.% to about 15 wt.%, based on the total weight of the anode composition.
11. The anode composition of any preceding claim, wherein the anode composition further comprises one or more conductive materials.
12. The anode composition of claim 11, wherein the amount of conductive material present in the anode composition is between about 2.5 wt.% and about 40 wt.%, based on the total weight of the anode composition.
13. The anode composition according to any one of the preceding claims, wherein the microsilicon active material particles or the anode composition are pre-lithiated.
14. The anode composition of claim 13, wherein the micro-silicon active material particles are pre-lithiated prior to incorporation into the anode composition.
15. The anode composition of claim 13 or claim 14, wherein the pre-lithiation level of the micro-silicon active material particles and / or the anode composition is between about 1% and about 30%.
16. The anode composition of any one of claims 13 to 15, wherein the pre-lithiation level of the micro-silicon active material particles is between about 10% and about 30%.
17. The anode composition of any one of the preceding claims, wherein the anode composition is a coating or film applied to the surface of a current collector material.
18. The anode composition of claim 17, wherein the current collector material is selected from the group comprising copper, aluminum, stainless steel, titanium, carbon, perforated metal foils, metal foams, and porous and non-porous films based on metal-coated polymers.
19. The anode composition of any preceding claim, wherein the anode composition is an anode for an electrochemical cell.
20. The anode composition of any preceding claim, wherein the anode composition is an anode of a primary or secondary battery.
21. The anode composition of any preceding claim, wherein the anode composition is an anode of a lithium ion battery.
22. An electrochemical cell comprising: an anode; a cathode; an electrolyte; and a separator, wherein the anode comprises the anode composition according to any one of claims 1 to 21, The lithium uptake capacity of the anode is greater than the lithium release capacity of the cathode.
23. The electrochemical cell of claim 22, wherein the capacity of the lithium uptake capacity of the anode is not fully utilized during charging of the lithium ion battery.
24. An electrochemical cell according to claim 22 or claim 23, wherein the anode is only partially lithiated in a fully charged state.
25. The electrochemical cell of any one of claims 22 to 24, wherein the degree of lithiation of the anode is limited to about 20% to about 80%.
26. The full cell assembly of any one of claims 22 to 25, wherein the capacity ratio (N / P ratio) of the anode to the cathode is between about 1.05 and about 7.
27. The electrochemical cell of any one of claims 22 to 26, wherein the capacity ratio of the anode to the cathode (N / P ratio) is between about 1.5 and about 4.
28. The electrochemical cell of any one of claims 22 to 27, wherein the capacity ratio of the anode to the cathode (N / P ratio) is between about 1.8 and about 3.
5.
29. The electrochemical cell of any one of claims 22 to 28, wherein the lower cutoff voltage is between about 2.5V and 3.0V.
30. The electrochemical cell of any one of claims 22 to 29, wherein the anode is pre-lithiated.
31. The electrochemical cell of claim 30, wherein the pre-lithiation level of the anode is between about 1% and about 30%.
32. An electrochemical cell according to any one of claims 22 to 31, wherein the cathode is selected from the group comprising lithium nickel cobalt manganese oxide (NCM), lithium iron phosphate (LFP), lithium nickel manganese spinel (LNMO), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium cobalt oxide (LCO) and sulfur composites.
33. The electrochemical cell according to any one of claims 22 to 32, wherein the electrolyte is selected from a non-aqueous electrolyte solution comprising one or more lithium salts.
34. The electrochemical cell of any one of claims 22 to 33, wherein the electrochemical cell is an energy storage device.
35. The electrochemical cell of claim 34, wherein the energy storage device is a battery, preferably a secondary battery.
36. The electrochemical cell of claim 35, wherein the battery is a lithium ion battery.
37. A method for improving the cycling stability of a lithium ion battery having an anode and a cathode, at least one electrolyte and a separator, wherein the anode composition is as defined in any one of claims 1 to 21.
38. The method of claim 37, wherein the anode within the battery delivers a specific capacity of at least about 450 mAh / g, 500 mAh / g, 600 mAh / g, 800 mAh / g, 1000 mAh / g, 1200 mAh / g, or 1500 mAh / g, and retains at least about 80% of its initial capacity after 100, 200, 400, 600, 800, 1000, or 1500 cycles of the battery.
39. Use of an anode composition in an electrochemical cell, wherein the anode composition is at least partly applied to a current collector material, and wherein the anode composition is as defined in any one of claims 1 to 21.
40. A method for preparing an anode of an electrochemical cell, the method comprising the steps of: (i) preparing an anode slurry comprising microsilicon active material particles, optionally one or more additional active materials, optionally one or more binders, optionally one or more conductive materials, optionally one or more additives and a solvent system; and (ii) casting a layer of said anode slurry onto a current collector material to provide a layer of wet anode composition on said current collector material, The microsilicon active material particles have one or more of the following: (i) a BET surface area of about 0.1 m 2 / g and about 10m 2 / g; (ii) D 50 The particle size is between about 0.1 μm and about 10 μm; and (iii) D 50 The ratio of the BET surface area is between about 0.1 and about 10.
41. The method of claim 41, wherein the method further comprises the step (iii) curing the wet anode layer by (a) solvent evaporation and / or (b) heat treatment to provide a dry anode composition layer coated on the current collector material.
42. The method of claim 40 or 41, wherein the binder content in the anode slurry is between about 2.5 wt.% and about 15 wt.% based on the total weight of the anode composition.
43. The method of any one of claims 40 to 42, wherein the content of conductive material in the anode slurry is between about 2.5 wt.% and about 40 wt.%, based on the total weight of the anode composition.
44. The method of any one of claims 40 to 43, wherein the viscosity of the anode slurry at a given shear rate is in the range between 500 mPas and 100,000 mPas.
45. The method of any one of claims 40 to 44, wherein the thickness of the dry anode composition layer ranges between about 5 μm and about 70 μm.
46. The method of any one of claims 41 to 45, wherein the temperature of step (iii)(a) is between about 40°C and 60°C.
47. The method of any one of claims 41 to 46, wherein the temperature of step (iii)(b) is between about 90°C and 180°C.
48. An anode comprising the anode composition according to any one of claims 1 to 21, wherein the anode is prepared according to the method according to any one of claims 40 to 47.
49. A method for assembling an electrochemical cell, wherein the method comprises the steps of: The method of any one of claims 41 to 49 for preparing an anode, wherein the anode comprises an anode composition according to any one of claims 1 to 21; and assembling the anode into an electrochemical cell.
